Surface protection film
By using an adhesive layer containing base polymer, ionic compound and fluorine-based compound in the surface protection film, the problem of static electricity generated during the peeling process is solved, and effective protection of optical and electronic components is achieved.
Patent Information
- Application Number
- CN202210418403.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2021-01-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-01-27
AI Technical Summary
The existing surface protection film is prone to static electricity during the peeling process, resulting in damage to optical and electronic components, and it is difficult to effectively prevent the generation of static electricity.
A surface protection film containing an adhesive layer is used, wherein the adhesive consists of a base polymer, an ionic compound and a fluorine-based compound. The surface free energy of the adhesive layer is in the range of 6 mJ/m2 to 30 mJ/m2 to suppress the peeling static voltage.
Effectively suppress the peeling static voltage, prevent damage to optical and electronic components, and improve the antistatic properties of the surface protection film.
Smart Images

Figure CN114716944B_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of January 27, 2021, an application number of 202110111988.9, and an invention name of surface protection film. Technical Field
[0002] The present invention relates to a surface protection film. Background Art
[0003] In the manufacturing process of optical components and electronic components, in order to prevent the surface damage of the optical components and the electronic components during processing, assembly, inspection, transportation, etc., a surface protection film is usually attached to the exposed surface of the optical components and the electronic components. Such a surface protection film is peeled off from the optical components and the electronic components when surface protection is no longer needed (Patent Document 1).
[0004] Generally, surface protection films, optical components, and electronic components have high electrical insulation properties, and static electricity is generated due to friction and peeling. Therefore, when peeling the surface protection film from the optical components and electronic components, static electricity is also easily generated. In such a case, for example, if a voltage is applied to the liquid crystal in a state where static electricity remains, there is a risk of orientation loss of the liquid crystal molecules or defects in the panel. In addition, the presence of static electricity may also become a factor that attracts dust and reduces operability.
[0005] In order to prevent static electricity, the surface protection film is generally subjected to an antistatic treatment. For example, the following technology is reported: the surface layer (top coating layer, back layer) of the surface protection film is provided with an antistatic function by forming an antistatic layer and applying an antistatic coating (Patent Documents 2 and 3).
[0006] In order to impart antistatic properties to the adhesive layer itself constituting the surface protection film, a method is being developed in which an ionic compound such as an alkali metal salt or an ionic liquid that functions as an antistatic agent is contained in the adhesive layer and then transferred to an adherend (Patent Document 4).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-17109
[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-223923
[0011] Patent Document 3: Japanese Patent Application Publication No. 2008-255332
[0012] Patent Document 4: Japanese Patent Application Laid-Open No. 9-165460 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] The purpose of the present invention is to provide a surface protection film, which includes an adhesive layer and is typically adhered to the exposed surface of the optical component and the electronic component in order to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical component and the electronic component, and the surface protection film fully suppresses the peeling static voltage and will not damage the optical component and the electronic component during peeling.
[0015] Solutions for solving problems
[0016] The surface protection film according to an embodiment of the present invention includes a pressure-sensitive adhesive layer.
[0017] The adhesive constituting the adhesive layer is formed of an adhesive composition.
[0018] The adhesive composition comprises a base polymer, an ionic compound, and a fluorine compound.
[0019] The surface free energy of the adhesive layer surface with respect to diiodomethane is 6 mJ / m 2 ~30mJ / m 2 .
[0020] In one embodiment, the content ratio of the ionic compound is 0.2 parts by weight or more based on 100 parts by weight of the base polymer.
[0021] In one embodiment, the content of the fluorine-based compound is 0.05 parts by weight or more based on 100 parts by weight of the base polymer.
[0022] In one embodiment, the base polymer is at least one selected from polyols, urethane prepolymers, acrylic resins, rubber resins, and silicone resins.
[0023] In one embodiment, after the adhesive layer contained in the surface protection film is bonded to a glass plate and left at a temperature of 23° C. for 30 minutes, the surface protection film is peeled off from the glass plate at a peeling angle of 180 degrees and a peeling speed of 300 mm / min at a temperature of 23° C., and the peeling force is 0.005 N / 25 mm to 0.1 N / 25 mm.
[0024] The optical member according to the embodiment of the present invention has the above-mentioned surface protection film bonded thereto.
[0025] The electronic component according to the embodiment of the present invention has the above-mentioned surface protection film bonded thereto.
[0026] Effects of the Invention
[0027] According to the present invention, a surface protection film can be provided, which includes an adhesive layer and is typically adhered to the exposed surface of the optical component and the electronic component in order to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical component and the electronic component, and the adhesive layer sufficiently suppresses the peeling static voltage and will not damage the optical component and the electronic component during peeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention.
[0029] Description of Reference Numerals
[0030] 1. Substrate layer
[0031] 2 Adhesive layer
[0032] 10 Surface protection film DETAILED DESCRIPTION
[0033] 《《A. Surface protection film》》
[0034] The surface protection film according to the embodiment of the present invention includes a pressure-sensitive adhesive layer.
[0035] As long as the surface protection film includes the adhesive layer, any other appropriate member may be included within a range that does not impair the effects of the present invention. Typically, the surface protection film of the present invention includes a substrate layer and an adhesive layer.
[0036] Figure 1 This is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. Figure 1 In the embodiment, the surface protection film 10 comprises a base material layer 1 and an adhesive layer 2. Figure 1 In the embodiment, the substrate layer 1 and the adhesive layer 2 are directly laminated.
[0037] exist Figure 1 In order to protect the adhesive layer 2 until use, any appropriate release liner (sometimes also referred to as release sheet or separator) (not shown) may be provided on the surface of the adhesive layer 2 on the opposite side to the substrate layer 1. Examples of the release liner include a release liner on the surface of a substrate (liner substrate) such as paper or plastic film treated with silicone, and a release liner on the surface of a substrate (liner substrate) such as paper or plastic film laminated with a polyolefin resin.
[0038] Examples of the plastic film used as the backing substrate include polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.
[0039] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, further preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.
[0040] The thickness of the surface protection film is preferably 5 μm to 500 μm, more preferably 10 μm to 450 μm, further preferably 15 μm to 400 μm, and particularly preferably 20 μm to 300 μm.
[0041] The surface free energy of the adhesive layer contained in the surface protection film with respect to diiodomethane is 6 mJ / m 2 ~30mJ / m 2 , more preferably 8mJ / m 2 ~30mJ / m 2 , more preferably 10mJ / m 2 ~30mJ / m 2 , particularly preferably 12 mJ / m 2 ~30mJ / m 2 . If the surface free energy of the adhesive layer contained in the surface protection film relative to diiodomethane is within the above range, it is possible to provide a surface protection film that can fully suppress the peeling static voltage and will not damage the adherend (representatively optical components and electronic components) during peeling. If the surface free energy of the adhesive layer contained in the surface protection film relative to diiodomethane deviates from the above range and is too low, there is a risk that the peeling static voltage cannot be fully suppressed. If the surface free energy of the adhesive layer contained in the surface protection film relative to diiodomethane deviates from the above range and is too high, there is a risk of contaminating the adherend.
[0042] It should be noted that the surface free energy of the adhesive layer contained in the surface protection film relative to diiodomethane can be easily measured as described later, and by designing the adhesive layer in a manner such that the surface free energy falls within the above-mentioned specified range, it is possible to provide a surface protection film that fully suppresses the peeling static voltage and does not damage the adherend (representatively optical components and electronic components) during peeling. Here, as the design point of the above-mentioned adhesive layer, in the present invention, it is representatively a combination of ionic compounds and fluorine compounds, and fluorine compounds. In addition, as a choice of fluorine compounds, for example, a fluorine compound that makes the above-mentioned surface free energy fall within the above-mentioned specified range can be cited, and such a choice is an act that can be implemented by a person skilled in the art even without repeated excessive trial and error.
[0043] With respect to the adhesive layer contained in the surface protection film, after being attached to a glass plate and placed at a temperature of 23° C. for 30 minutes, the peeling force when the surface protection film is peeled off from the glass plate at a peeling angle of 180 degrees and a peeling speed of 300 mm / min at a temperature of 23° C. is preferably 0.005N / 25mm to 0.1N / 25mm, more preferably 0.007N / 25mm to 0.08N / 25mm, further preferably 0.01N / 25mm to 0.05N / 25mm, particularly preferably 0.01N / 25mm to 0.03N / 25mm, and most preferably 0.01N / 25mm to 0.02N / 25mm. If the peeling force is within the above range, it is possible to provide a surface protection film that is not easily peeled off from an adherend, is not easily peeled off after being attached to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component, and can be easily peeled off when peeling is required.
[0044] The surface protection film can be manufactured by any appropriate method. As such a manufacturing method, for example, it can be carried out by any appropriate manufacturing method such as the following method:
[0045] (1) A method of applying a solution or hot melt of a material for forming an adhesive layer onto a substrate layer;
[0046] (2) A method of applying a solution or hot melt of a material for forming an adhesive layer onto a separator and transferring the formed adhesive layer onto a substrate layer;
[0047] (3) A method of extruding a material for forming an adhesive layer and coating it on a substrate layer;
[0048] (4) A method of extruding the substrate layer and the adhesive layer in two or more layers,
[0049] (5) A method of laminating a single adhesive layer on a substrate layer or a method of laminating a double adhesive layer together with a laminating layer;
[0050] (6) A method of laminating an adhesive layer and a base material such as a film or a laminating layer in two or more layers.
[0051] As the coating method, for example, a roll coating method, a comma coating method, a die coating method, a reverse coating method, a screen printing method, a gravure coating method, etc. can be used.
[0052] The surface protection film of an embodiment of the present invention includes an adhesive layer, which is typically adhered to the exposed surface of the optical component and the electronic component in order to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical component and the electronic component, and it fully suppresses the peeling static voltage and will not damage the optical component and the electronic component during peeling.
[0053] The surface protection film of the embodiment of the present invention preferably has a peeling static voltage to glass of 3.0 kV or less, more preferably 2.5 kV or less, further preferably 2.0 kV or less, particularly preferably 1.7 kV or less, and most preferably 1.5 kV or less. The method for measuring the peeling static voltage to glass will be described later.
[0054] The peeling electrostatic voltage of the surface protection film of the embodiment of the present invention to the acrylic plate is preferably 4.0 kV or less, more preferably 3.5 kV or less, further preferably 3.0 kV or less, further preferably 2.5 kV or less, particularly preferably 2.0 kV or less, and most preferably 1.5 kV or less. The method for measuring the peeling electrostatic voltage to the acrylic plate will be described later.
[0055] The haze of the surface protection film of the embodiment of the present invention is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, particularly preferably 2.8% or less, and most preferably 2.5% or less. If the haze of the surface protection film of the embodiment of the present invention is within the above range, it becomes a surface protection film suitable for being attached to the exposed surface of optical components and electronic components. In particular, if the haze of the surface protection film of the embodiment of the present invention can be reduced to 3% or less, the inspection property of the surface protection film of the embodiment of the present invention is further improved, and therefore it is more preferred. The method for measuring the haze will be described later.
[0056] The residual adhesion of the surface protection film of the embodiment of the present invention to the glass is preferably 70% or more, more preferably 80% or more, further preferably 85% or more, particularly preferably 88% or more, and most preferably 90% or more. The residual adhesion to the glass is an indicator of the degree to which the components of the adhesive layer of the surface protection film are transferred to the adherend and the surface is contaminated. The higher the value of the residual adhesion to the glass, the greater the concern of contaminating the adherend is for the surface protection film, and the lower the value of the residual adhesion to the glass, the less the concern of contaminating the adherend is for the surface protection film. The method for measuring the residual adhesion to the glass will be described later.
[0057] 《A-1. Adhesive layer》
[0058] The adhesive layer is composed of an adhesive. The adhesive is formed from an adhesive composition. That is, the adhesive layer is formed by forming an adhesive composed of an adhesive composition into a layer.
[0059] Adhesives can be specified as substances formed from adhesive compositions. This is because adhesives are formed by cross-linking reactions of adhesive compositions by heating, ultraviolet irradiation, etc., so adhesives cannot be specified directly by their structure. In addition, there are situations where this is almost unrealistic ("impossible / unrealistic situations"). Therefore, the adhesive is properly specified as a "substance" through the definition of "substance formed from adhesive compositions".
[0060] Adhesive layer can be formed by any appropriate method. As such method, for example, the following method can be cited: adhesive composition is coated on any appropriate substrate, heated and dried as required, and solidified as required, thereby forming adhesive layer on the substrate. As such coating method, for example, methods such as gravure roll coating, reverse roll coating, kiss roll coating, dip roll coating, rod coating, blade coating, air knife coating, spray coating, comma coating, direct coating, roller brush coating can be cited.
[0061] From the viewpoint of further expressing the effects of the present invention, the thickness of the adhesive layer is preferably 0.5 μm to 150 μm, more preferably 1 μm to 100 μm, further preferably 2 μm to 80 μm, particularly preferably 3 μm to 50 μm, and most preferably 5 μm to 30 μm.
[0062] The adhesive composition includes a base polymer, an ionic compound, and a fluorine-based compound. By making the adhesive composition include a base polymer, an ionic compound, and a fluorine-based compound, the following surface protection film can be provided: comprising an adhesive layer and typically adhered to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc., and fully suppressing the peeling static voltage, and not damaging the optical component and the electronic component during peeling.
[0063] In the present invention, the adhesive composition includes both ionic compounds and fluorine compounds in addition to the base polymer, so that the effect of the present invention can be shown. In particular, by including both (combined use) of the fluorine compounds (sometimes referred to as "specific fluorine compounds") of the preferred embodiment described later, the effect of the present invention can be significantly shown. It is inferred that the reason is that by making the ionic compound and the fluorine compound (preferably specific fluorine compound) that can show antistatic effect be present in the adhesive composition at the same time, so that the ionic compound is distributed on the surface side of the adhesive layer (the side that is attached to the adherend) by the synergistic effect with the fluorine compound (preferably specific fluorine compound).
[0064] The content ratio of the base polymer in the adhesive composition is preferably 60% to 99.9% by weight, more preferably 65% to 99.9% by weight, further preferably 70% to 99.9% by weight, particularly preferably 75% to 99.9% by weight, and most preferably 80% to 99.9% by weight, based on the solid content. If the content ratio of the base polymer in the adhesive composition is within the above range based on the solid content, a surface protective film that fully suppresses peeling static voltage and does not damage adherends (representatively optical components and electronic components) during peeling can be provided.
[0065] The content ratio of the ionic compound relative to 100 parts by weight of the base polymer is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight to 5.0 parts by weight, further preferably 0.5 parts by weight to 3.0 parts by weight, particularly preferably 0.7 parts by weight to 2.0 parts by weight, and most preferably 0.8 parts by weight to 1.5 parts by weight. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer is within the above range, it is possible to provide a surface protective film that fully suppresses the peeling static voltage and does not damage the adherend (representatively optical components and electronic components) during peeling. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer deviates from the above range and is too low, there is a risk of not being able to fully suppress the peeling static voltage. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer deviates from the above range and is too high, there is a risk of contaminating the adherend.
[0066] The content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is preferably 0.05 parts by weight or more, more preferably 0.1 parts by weight to 5.0 parts by weight, further preferably 0.15 parts by weight to 3.0 parts by weight, particularly preferably 0.2 parts by weight to 2.0 parts by weight, and most preferably 0.23 parts by weight to 1.5 parts by weight. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is within the above range, it is possible to provide a surface protection film that fully suppresses the peeling static voltage and does not damage the adherend (representatively optical components and electronic components) during peeling. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer deviates from the above range and is too low, there is a risk of not being able to fully suppress the peeling static voltage. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer deviates from the above range and is too high, there is a risk of contaminating the adherend.
[0067] <A-1-1. Base polymer>
[0068] The base polymer is preferably at least one selected from urethane resins, acrylic resins, rubber resins, and silicone resins. If the base polymer is at least one selected from urethane resins, acrylic resins, rubber resins, and silicone resins, it is possible to provide a surface protection film that can more fully suppress peeling static voltage and will not damage adherends (representatively optical components and electronic components) during peeling.
[0069] [A-1-1-1. Polyol]
[0070] The polyol preferably reacts with a polyfunctional isocyanate compound to form a carbamate resin. More specifically, the carbamate resin is preferably formed from a composition containing a polyol and a polyfunctional isocyanate compound, and more specifically, the carbamate resin is formed by curing the composition containing a polyol and a polyfunctional isocyanate compound. As a method for curing a composition containing a polyol and a polyfunctional isocyanate compound to form a carbamate resin, any appropriate method such as a carbamate reaction method using bulk polymerization, solution polymerization, etc. can be adopted within the scope that does not impair the effect of the present invention.
[0071] The polyol may be used alone or in combination of two or more.
[0072] The polyol is preferably at least one selected from polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, and castor oil polyol. From the viewpoint of further exhibiting the effects of the present invention, the polyol is more preferably a polyether polyol.
[0073] The polyester polyol can be obtained, for example, by an esterification reaction between a polyol component and an acid component.
[0074] Examples of the polyol component include ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerin, trimethylolpropane, pentaerythritol, hexanetriol, and polypropylene glycol.
[0075] Examples of the acid component include succinic acid, methylsuccinic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, dimer acid, 2-methyl-1,4-cyclohexanedicarboxylic acid, 2-ethyl-1,4-cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalene dicarboxylic acid, 4,4′-biphenyl dicarboxylic acid, and anhydrides thereof.
[0076] Examples of the polyether polyol include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide using water, low molecular weight polyols (propylene glycol, ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, etc.), bisphenols (bisphenol A, etc.), dihydroxybenzenes (catechol, resorcinol, hydroquinone, etc.), etc. as initiators. Specifically, examples include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0077] Examples of the polycaprolactone polyol include caprolactone polyester diols obtained by ring-opening polymerization of cyclic ester monomers such as ε-caprolactone and σ-valerolactone.
[0078] Examples of the polycarbonate polyol include: polycarbonate polyols obtained by subjecting the above polyol components to a polycondensation reaction with phosgene; polycarbonate polyols obtained by subjecting the above polyol components to an ester exchange condensation reaction with a carbonic acid diester such as dimethyl carbonate, diethyl carbonate, dipropyl carbonate, diisopropyl carbonate, dibutyl carbonate, ethylbutyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, and dibenzyl carbonate; copolymerized polycarbonate polyols obtained by using two or more of the above polyol components in combination; polycarbonate polyols obtained by subjecting the above various polycarbonate polyols to an esterification reaction with a carboxyl group-containing compound; polycarbonate polyols; polycarbonate polyols obtained by etherification reaction of the above-mentioned various polycarbonate polyols with hydroxyl-containing compounds; polycarbonate polyols obtained by ester exchange reaction of the above-mentioned various polycarbonate polyols with ester compounds; polycarbonate polyols obtained by ester exchange reaction of the above-mentioned various polycarbonate polyols with hydroxyl-containing compounds; polyester polycarbonate polyols obtained by condensation reaction of the above-mentioned various polycarbonate polyols with dicarboxylic acid compounds; copolyether polycarbonate polyols obtained by copolymerizing the above-mentioned various polycarbonate polyols with alkylene oxides; etc.
[0079] Examples of castor oil-based polyols include castor oil-based polyols obtained by reacting castor oil fatty acids with the above-mentioned polyol components. Specifically, examples thereof include castor oil-based polyols obtained by reacting castor oil fatty acids with polypropylene glycol.
[0080] The number average molecular weight Mn of the polyol is preferably 300 to 100000, more preferably 400 to 75000, further preferably 450 to 50000, and particularly preferably 500 to 30000. If the number average molecular weight Mn of the polyol is within the above range, it is possible to provide a surface protection film that is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of an optical component or an electronic component in a typical manufacturing process of an optical component or an electronic component, and can be more easily peeled off when peeling is required.
[0081] The polyol preferably contains a polyol (A1) having three OH groups and having a number average molecular weight Mn of 300 to 100000. The polyol (A1) may be one type or two or more types.
[0082] The content of the polyol (A1) in the polyol is preferably 5% by weight or more, more preferably 25% by weight to 100% by weight, further preferably 50% by weight to 100% by weight, particularly preferably 70% by weight to 100% by weight, and most preferably 90% by weight to 100% by weight. If the content of the polyol (A1) in the polyol is within the above range, a surface protection film can be provided which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of the optical component or the electronic component in the manufacturing process of the optical component or the electronic component, and can be more easily peeled off when peeling is required.
[0083] As the polyol (A1), it is preferred to contain a polyol (A1a) having three OH groups and having a number average molecular weight Mn of 8000 to 20000. The polyol (A1a) may be one type or two or more types.
[0084] The content of the polyol (A1a) in the polyol (A1) is preferably 50% by weight or more, more preferably 60% to 100% by weight, further preferably 70% to 95% by weight, particularly preferably 75% to 93% by weight, and most preferably 80% to 90% by weight. If the content of the polyol (A1a) in the polyol (A1) is within the above range, a surface protection film can be provided which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of an optical component or an electronic component in a typical manufacturing process of an optical component or an electronic component, and can be more easily peeled off when peeling is required.
[0085] The number average molecular weight Mn of the polyol (A1a) is 8000 to 20000, preferably 8000 to 18000, more preferably 8500 to 17000, further preferably 9000 to 16000, particularly preferably 9500 to 15500, and most preferably 10000 to 15000. When the number average molecular weight Mn of the polyol (A1a) is within the above range, a surface protection film can be provided which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of an optical member or an electronic member in a manufacturing process of the optical member or the electronic member, and can be peeled off more easily when peeling is required.
[0086] The polyol (A1) may contain a polyol (A1b) having three or more OH groups and having a number average molecular weight Mn of not more than 5000. The polyol (A1b) may be one type or two or more types.
[0087] The polyol (A1b) is preferably at least one selected from a polyol having three OH groups (triol), a polyol having four OH groups (tetraol), a polyol having five OH groups (pentaol), and a polyol having six OH groups (hexaol).
[0088] The content of the polyol (A1b) in the polyol (A1) is preferably 50% by weight or less, more preferably 0% to 40% by weight, further preferably 5% to 30% by weight, particularly preferably 7% to 25% by weight, and most preferably 10% to 20% by weight. If the content of the polyol (A1b) in the polyol (A1) is within the above range, a surface protection film can be provided which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of an optical component or an electronic component in a typical manufacturing process of an optical component or an electronic component, and can be more easily peeled off when peeling is required.
[0089] The number average molecular weight Mn of the polyol (A1b) is preferably 500 to 5000, more preferably 600 to 4500, further preferably 700 to 4000, particularly preferably 800 to 3500, and most preferably 900 to 3300. If the number average molecular weight Mn of the polyol (A1b) is within the above range, it is possible to provide a surface protection film that is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component, and can be more easily peeled off when peeling is required. If the number average molecular weight Mn of the polyol (A1b) deviates from the above range, there is a risk that the adhesive force may increase over time, and there is a risk that excellent reprocessability may not be exhibited.
[0090] When the polyol (A1b) is at least one selected from a polyol having 4 OH groups (tetraol), a polyol having 5 OH groups (pentaol), and a polyol having 6 OH groups (hexaol), the total amount thereof is preferably 40% by weight or less, more preferably 0% to 30% by weight, further preferably 3% to 20% by weight, particularly preferably 5% to 15% by weight, and most preferably 7% to 10% by weight, based on the content ratio in the polyol (A1). In the polyol (A1), when the polyol (A1b) is at least one selected from a polyol having 4 OH groups (tetraol), a polyol having 5 OH groups (pentaol), and a polyol having 6 OH groups (hexaol), and the total amount thereof is within the above range, it is possible to provide a surface protection film which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of an optical member or an electronic member in a production process of the optical member or the electronic member, and can be peeled off more easily when peeling is required. In addition, a surface protection film having excellent transparency can be obtained.
[0091] In the polyol (A1b), the content ratio of at least one selected from the group consisting of a polyol (tetrahydric alcohol) having 4 OH groups, a polyol (pentahydric alcohol) having 5 OH groups, and a polyol (hexahydric alcohol) having 6 OH groups is preferably less than 10% by weight, more preferably 7% by weight or less, further preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less relative to the entire polyol (A1). If the content ratio of at least one selected from the group consisting of a polyol (tetrahydric alcohol) having 4 OH groups, a polyol (pentahydric alcohol) having 5 OH groups, and a polyol (hexahydric alcohol) having 6 OH groups in the polyol (A1b) is within the above range, a surface protective film can be provided which is less likely to be peeled off from an adherend, is less likely to be peeled off after being attached to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component, and can be more easily peeled off when peeling is required. If the content ratio of at least one selected from a polyol having four OH groups (tetrahydric alcohol), a polyol having five OH groups (pentahydric alcohol), and a polyol having six OH groups (hexahydric alcohol) in the polyol (A1b) deviates from the above range, the transparency of the surface protection film may be reduced.
[0092] The polyol (A1) may contain a polyol (A1c) having 4 or more OH groups and having a number average molecular weight Mn of 20000 or less. The polyol (A1c) may be used alone or in combination of two or more.
[0093] The content ratio of the polyol (A1c) having a number average molecular weight Mn of 4 or more OH groups of less than 20000 is preferably less than 70% by weight, more preferably less than 60% by weight, further preferably less than 50% by weight, particularly preferably less than 40% by weight, and most preferably less than 30% by weight. If the content ratio of the polyol (A1) having a number average molecular weight Mn of 4 or more OH groups of less than 20000 is within the above range, it is possible to provide a surface protective film that is less likely to be easily peeled off from the adherend, representatively in the manufacturing process of optical components and electronic components, after being attached to the exposed surface of the optical components and the electronic components, and can be more easily peeled off when peeling is required. In addition, it can be a surface protective film with excellent transparency.
[0094] [A-1-1-2. Urethane prepolymer]
[0095] The carbamate prepolymer preferably reacts with a polyfunctional isocyanate compound to form a carbamate resin. More specifically, the carbamate resin is preferably formed from a composition containing a carbamate prepolymer and a polyfunctional isocyanate compound, and more specifically, the carbamate resin is formed by curing the composition containing a carbamate prepolymer and a polyfunctional isocyanate compound. As a method for curing a composition containing a polyol and a polyfunctional isocyanate compound to form a carbamate resin, any appropriate manufacturing method may be used as long as it is a method for manufacturing a carbamate resin using a so-called "carbamate prepolymer" as a raw material.
[0096] In the description of the present invention, the "urethane prepolymer" is what is generally referred to as "urethane prepolymer" by those skilled in the art in the production of urethane resin, and is different from the "polyol" described in the section A-1-1-1.
[0097] The urethane prepolymer may be used alone or in combination of two or more.
[0098] The number average molecular weight Mn of the urethane prepolymer is preferably 3,000 to 1,000,000.
[0099] The urethane prepolymer is preferably a polyurethane polyol, more preferably a product obtained by reacting a polyester polyol (a1) or a polyether polyol (a2) alone or in the form of a mixture of (a1) and (a2) with a polyfunctional isocyanate compound in the presence or absence of a catalyst. The polyester polyol (a1) may be one or more. The polyether polyol (a2) may be one or more.
[0100] As polyester polyol (a1), any appropriate polyester polyol can be used. As such polyester polyol (a1), for example, polyester polyol obtained by reacting an acid component with a diol component can be cited. As an acid component, for example, terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, trimellitic acid, etc. can be cited. As a diol component, for example, ethylene glycol, propylene glycol, diethylene glycol, butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, butyl ethyl pentanediol can be cited. As a polyol component, glycerol, trimethylolpropane, pentaerythritol, etc. can be cited. Examples of the polyester polyol (a1) include polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone) and polyvalerolactone.
[0101] As the molecular weight of the polyester polyol (a1), any molecular weight from low molecular weight to high molecular weight can be used. As the molecular weight of the polyester polyol (a1), the number average molecular weight Mn is preferably 100 to 100,000. When the number average molecular weight Mn is less than 100, there is a risk that the reactivity becomes high and gelation becomes easy to occur. When the number average molecular weight Mn exceeds 100,000, there is a risk that the reactivity becomes low and the cohesive force of the polyurethane polyol itself becomes small. The amount of polyester polyol (a1) used is preferably 0 mol% to 90 mol% in the polyol constituting the polyurethane polyol.
[0102] As the polyether polyol (a2), any appropriate polyether polyol can be used. As such a polyether polyol (a2), for example, a polyether polyol obtained by polymerizing an oxirane compound such as ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, etc. using a low molecular weight polyol such as water, propylene glycol, ethylene glycol, glycerol, trimethylolpropane as an initiator can be cited. As such a polyether polyol (a2), specifically, for example, a polyether polyol having a functional group number of 2 or more such as polypropylene glycol, polyethylene glycol, polytetramethylene glycol can be cited.
[0103] As the molecular weight of the polyether polyol (a2), any molecular weight from low molecular weight to high molecular weight can be used. As the molecular weight of the polyether polyol (a2), the number average molecular weight Mn is preferably 100 to 100,000. When the number average molecular weight Mn is less than 100, there is a risk that the reactivity becomes high and gelation becomes easy to occur. When the number average molecular weight Mn exceeds 100,000, there is a risk that the reactivity becomes low and the cohesive force of the polyurethane polyol itself becomes small. The amount of the polyether polyol (a2) used is preferably 0 mol% to 90 mol% in the polyol constituting the polyurethane polyol.
[0104] The polyether polyol (a2) may be partially replaced with diols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerol, trimethylolpropane, and pentaerythritol, or polyamines such as ethylenediamine, N-aminoethylethanolamine, isophoronediamine, and xylylenediamine, and used in combination as necessary.
[0105] As polyether polyol (a2), only bifunctional polyether polyol can be used, or a polyether polyol having a number average molecular weight Mn of 100 to 100,000 and having at least 3 or more hydroxyl groups in one molecule can be used in part or in whole. When a polyether polyol having a number average molecular weight Mn of 100 to 100,000 and having at least 3 or more hydroxyl groups in one molecule is used in part or in whole as polyether polyol (a2), the balance between adhesive force and removability can be improved. For such polyether polyol, when the number average molecular weight Mn is less than 100, there is a risk that the reactivity becomes high and gelation becomes easy to occur. In addition, for such polyether polyol, when the number average molecular weight Mn exceeds 100,000, there is a risk that the reactivity becomes low and the cohesive force of the polyurethane polyol itself becomes small. The number average molecular weight Mn of such polyether polyol is more preferably 100 to 10,000.
[0106] Any appropriate catalyst can be used as a catalyst that can be used when obtaining polyurethane polyol. Examples of such a catalyst include tertiary amine compounds and organic metal compounds.
[0107] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undec-7-ene (DBU).
[0108] Examples of the organometallic compound include tin compounds and non-tin compounds.
[0109] Examples of the tin compound include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and 2-ethyltin hexanoate.
[0110] As non-tin compounds, for example, titanium compounds such as dibutyltitanium dichloride, tetrabutyl titanate, butoxytitanium trichloride, etc.; lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, lead naphthenate, etc.; iron compounds such as iron 2-ethylhexanoate, iron acetylacetonate, etc.; cobalt compounds such as cobalt benzoate, cobalt 2-ethylhexanoate, etc.; zinc compounds such as zinc naphthenate, zinc 2-ethylhexanoate, etc.; zirconium compounds such as zirconium naphthenate, etc.; etc.
[0111] When a catalyst is used to obtain polyurethane polyol, if it is a system of a single catalyst, in a system where there are two polyols, polyester polyol and polyether polyol, gelation or turbidity of the reaction solution is likely to occur due to the difference in their reactivity. Therefore, by using two catalysts when obtaining polyurethane polyol, it becomes easy to control the reaction rate, the selectivity of the catalyst, etc., and these problems can be solved. As a combination of such two catalysts, for example: tertiary amine / organic metal system, tin system / non-tin system, tin system / tin system, preferably tin system / tin system, more preferably a combination of dibutyltin dilaurate and 2-ethylhexanoate tin. For its blending ratio, in terms of weight ratio, 2-ethylhexanoate tin / dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6. When the blending ratio is 1 or more, there is a risk of gelation becoming easy to occur due to the balance of catalytic activity.
[0112] When a catalyst is used to obtain the polyurethane polyol, the amount of the catalyst used is preferably 0.01% by weight to 1.0% by weight based on the total amount of the polyester polyol (a1), the polyether polyol (a2) and the polyfunctional isocyanate compound.
[0113] When a catalyst is used to obtain polyurethane polyol, the reaction temperature is preferably lower than 100° C., more preferably 85° C. to 95° C. If the temperature is higher than 100° C., it may be difficult to control the reaction rate and crosslinking structure, and it may be difficult to obtain polyurethane polyol having a predetermined molecular weight.
[0114] When obtaining polyurethane polyol, a catalyst may not be used. In this case, the reaction temperature is preferably 100° C. or higher, more preferably 110° C. or higher. When obtaining polyurethane polyol without a catalyst, the reaction is preferably carried out for 3 hours or more.
[0115] As a method for obtaining polyurethane polyol, for example, the following methods can be cited: 1) a method of putting all the polyester polyol, polyether polyol, catalyst, and polyfunctional isocyanate compound into a flask; 2) a method of putting the polyester polyol, polyether polyol, and catalyst into a flask and adding the polyfunctional isocyanate compound dropwise. As a method for obtaining polyurethane polyol, the method 2) is preferred from the aspect of controlling the reaction.
[0116] Any appropriate solvent may be used when obtaining the polyurethane polyol. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone. Among these solvents, toluene is preferred.
[0117] [A-1-1-3. Acrylic resin]
[0118] As the acrylic resin, any appropriate acrylic resin can be adopted within a range that does not impair the effects of the present invention. The acrylic resin may be one type or two or more types.
[0119] From the viewpoint of further expressing the effects of the present invention, the weight average molecular weight of the acrylic resin is preferably 300,000 to 2.5 million, more preferably 350,000 to 2 million, further preferably 400,000 to 1.8 million, particularly preferably 500,000 to 1.5 million.
[0120] As the acrylic resin, from the viewpoint of further demonstrating the effects of the present invention, an acrylic resin formed by polymerization of a composition (B) comprising (component a) an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms in the alkyl ester moiety, and (component b) at least one selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid. (component a) and (component b) may each independently be one type or two or more types.
[0121] Examples of the alkyl (meth)acrylate (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms include n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are more preferred, from the viewpoint of further expressing the effects of the present invention.
[0122] As at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid, there can be mentioned, for example, (meth)acrylates having an OH group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, (meth)acrylic acid, etc. Among these, hydroxyethyl (meth)acrylate and (meth)acrylic acid are preferred, and hydroxyethyl acrylate and acrylic acid are more preferred, from the viewpoint of further expressing the effects of the present invention.
[0123] The composition (B) may contain a copolymerizable monomer other than the components (a) and (b). The copolymerizable monomer may be one kind or two or more kinds. Examples of such copolymerizable monomers include: carboxyl group-containing monomers such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (e.g., anhydride group-containing monomers such as maleic anhydride and itaconic anhydride) (except (meth)acrylic acid); amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; amino group-containing monomers such as aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; epoxy group-containing monomers such as glycidyl(meth)acrylate and methylglycidyl(meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinyl Heterocyclic vinyl monomers such as 1-aminopiperazine, N-vinylpyrrole, N-vinylimidazole, vinylpyridine, vinylpyrimidine, and vinyloxazole; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; imide group-containing monomers such as cyclohexylmaleimide and isopropylmaleimide; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylates having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ether; vinyl chloride; etc.
[0124] As copolymerizable monomers, multifunctional monomers can also be used. Multifunctional monomers refer to monomers having two or more ethylenically unsaturated groups in one molecule. As ethylenically unsaturated groups, any appropriate ethylenically unsaturated groups can be used within the scope of not damaging the effect of the present invention. As such ethylenically unsaturated groups, for example, free radical polymerizable functional groups such as vinyl, propenyl, isopropenyl, vinyl ether (vinyloxy), and allyl ether (allyloxy) can be cited. Examples of the multifunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. Such a multifunctional monomer may be used alone or in combination of two or more.
[0125] As the copolymerizable monomer, an alkoxyalkyl (meth)acrylate may also be used. Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The alkoxyalkyl (meth)acrylate may be one or more.
[0126] From the viewpoint of further exhibiting the effects of the present invention, the content of the (meth)acrylic acid alkyl ester (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms is preferably 30 wt% or more, more preferably 35 to 99 wt%, further preferably 40 to 98 wt%, and particularly preferably 50 to 95 wt%, based on the total amount (100 wt%) of the monomer components constituting the acrylic polymer.
[0127] From the viewpoint of further expressing the effects of the present invention, the content of at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid is preferably 1 wt% or more, more preferably 1 to 30 wt%, further preferably 2 to 20 wt%, and particularly preferably 3 to 10 wt%, based on the total amount (100 wt%) of the monomer components constituting the acrylic polymer.
[0128] Composition (B) can contain any appropriate other components within the scope of not damaging the effect of the present invention. As such other components, for example, polymerization initiator, chain transfer agent, solvent etc. can be cited. About the content of these other components, any appropriate content can be adopted within the scope of not damaging the effect of the present invention.
[0129] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc., depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.
[0130] It is preferred to use a thermal polymerization initiator when obtaining an acrylic resin by solution polymerization. As such a thermal polymerization initiator, for example, an azo polymerization initiator, a peroxide polymerization initiator (for example, dibenzoyl peroxide, tert-butyl permaleate, etc.), a redox polymerization initiator, etc. can be cited. Among these thermal polymerization initiators, the azo initiator disclosed in Japanese Patent Publication No. 2002-69411 is particularly preferred. From the perspective that the decomposition product of the polymerization initiator is the cause of the generation of gas (escape gas) generated by heating, and thus is not easy to remain in the acrylic resin, such an azo polymerization initiator is preferred. As an azo polymerization initiator, 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc. can be cited.
[0131] When obtaining the acrylic polymer by active energy ray polymerization, a photopolymerization initiator may be preferably used. Examples of the photopolymerization initiator include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators.
[0132] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. can be cited. As benzoin-based photopolymerization initiators, for example, benzoin, etc. can be cited. As benzyl-based photopolymerization initiators, for example, benzyl, etc. can be cited. As benzophenone-based photopolymerization initiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be cited. As ketal-based photopolymerization initiators, for example, benzyldimethylketal, etc. can be cited. As thioxanthone-based photopolymerization initiators, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be cited.
[0133] It should be noted that, when the base polymer is an acrylic resin, the adhesive composition may contain a crosslinking agent. By using a crosslinking agent, the cohesive force of the adhesive can be increased, and the effect of the present invention can be further demonstrated. The crosslinking agent may be only one or more than two.
[0134] Examples of the crosslinking agent include polyfunctional isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and amine crosslinking agents. Among these, at least one selected from the group consisting of polyfunctional isocyanate crosslinking agents and epoxy crosslinking agents is preferred from the viewpoint of further expressing the effects of the present invention.
[0135] Examples of the polyfunctional isocyanate crosslinking agent include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of the polyfunctional isocyanate crosslinking agent include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name “Coronate L”), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name “Coronate HL”), trade name “Coronate HX” (Nippon Polyurethane Industries, Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “TAKENATE 110N”).
[0136] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylene diamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitan. Alcohol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Commercial products such as trade name "TETRAD C" (Mitsubishi Gas Chemical Co., Ltd.) are also listed as epoxy crosslinking agents.
[0137] The content of the crosslinking agent in the adhesive composition can be any appropriate content within the range that does not impair the effect of the present invention. As such a content, for example, from the perspective of further demonstrating the effect of the present invention, it is preferably 0.05 to 20 parts by weight, more preferably 0.1 to 18 parts by weight, further preferably 0.5 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight relative to the solid content (100 parts by weight) of the acrylic resin.
[0138] [A-1-1-4. Rubber-based resin]
[0139] As the rubber resin, any appropriate rubber resin used in a known rubber adhesive such as described in JP-A-2015-074771 can be adopted within a range not impairing the effects of the present invention.
[0140] [A-1-1-5. Silicone resin]
[0141] As the silicone resin, any appropriate silicone resin used in a known silicone adhesive such as described in JP-A-2014-047280 may be used within a range not impairing the effects of the present invention.
[0142] <A-1-2. Urethane resin>
[0143] As described above, the polyol as the base polymer is preferably reacted with a polyfunctional isocyanate compound to form a carbamate resin. More specifically, the carbamate resin is preferably formed from a composition containing a polyol and a polyfunctional isocyanate compound, and more specifically, the carbamate resin is formed by curing the composition containing a polyol and a polyfunctional isocyanate compound. As a method for curing the composition containing a polyol and a polyfunctional isocyanate compound to form a carbamate resin, any appropriate method such as a carbamate reaction method using bulk polymerization, solution polymerization, etc. can be adopted within the scope that does not impair the effect of the present invention.
[0144] In addition, as described above, the carbamate prepolymer as the base polymer is preferably reacted with a polyfunctional isocyanate compound to form a carbamate resin. More specifically, the carbamate resin is preferably formed from a composition containing a carbamate prepolymer and a polyfunctional isocyanate compound, and more specifically, the carbamate resin is formed by curing the composition containing a carbamate prepolymer and a polyfunctional isocyanate compound. As a method for curing a composition containing a polyol and a polyfunctional isocyanate compound to form a carbamate resin, any appropriate manufacturing method can be used as long as it is a method for manufacturing a carbamate resin using a so-called "carbamate prepolymer" as a raw material.
[0145] That is, a preferred embodiment of the urethane resin is a urethane resin formed from a composition containing a polyol and a polyfunctional isocyanate compound. Another preferred embodiment of the urethane resin is a urethane resin formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound.
[0146] [A-1-2-1. Urethane resin formed from a composition containing a polyol and a polyfunctional isocyanate compound]
[0147] The polyfunctional isocyanate compound may be used alone or in combination of two or more.
[0148] As the polyfunctional isocyanate compound, any appropriate polyfunctional isocyanate compound that can be used in the urethanization reaction can be adopted. As such polyfunctional isocyanate compounds, for example, polyfunctional aliphatic isocyanate compounds, polyfunctional alicyclic isocyanates, polyfunctional aromatic isocyanate compounds, polyfunctional aromatic aliphatic isocyanate compounds, etc. can be cited.
[0149] Examples of the polyfunctional aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, 2,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0150] Examples of the polyfunctional alicyclic isocyanate compound include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanate methyl)cyclohexane, 1,4-bis(isocyanate methyl)cyclohexane, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0151] Examples of the polyfunctional aromatic diisocyanate compound include 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4′,4″-triphenylmethane triisocyanate, dianisidine diisocyanate, and xylylene diisocyanate.
[0152] Examples of the polyfunctional aromatic aliphatic isocyanate compound include ω,ω′-diisocyanate-1,3-dimethylbenzene, ω,ω′-diisocyanate-1,4-dimethylbenzene, ω,ω′-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.
[0153] Examples of the polyfunctional isocyanate compound include trimethylolpropane adducts of the various polyfunctional isocyanate compounds described above, biuret forms obtained by reaction with water, trimers having an isocyanurate ring, etc. These may also be used in combination.
[0154] The equivalent ratio of the NCO group to the OH group of the polyol and the polyfunctional isocyanate compound is preferably 5.0 or less, more preferably 0.1 to 3.0, more preferably 0.2 to 2.5, more preferably 0.3 to 2.5, more preferably 0.3 to 2.0, particularly preferably 0.5 to 2.0, and most preferably 0.5 to 1.8. If the equivalent ratio of the NCO group to the OH group is within the above range, it is possible to provide a surface protective film that will not be easily peeled off from the adherend, representatively, will not easily peel off after being attached to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component, and can be easily peeled off when peeling is required. In addition, if the equivalent ratio of the NCO group to the OH group is within the above range, the haze can be reduced. In particular, if the haze can be reduced to less than 3%, the inspection of the surface protective film of the embodiment of the present invention is further improved.
[0155] Regarding the content ratio of the polyfunctional isocyanate compound, the polyfunctional isocyanate compound is preferably 1.0% by weight to 30% by weight relative to the polyol, more preferably 1.5% by weight to 27% by weight, further preferably 2.0% by weight to 25% by weight, further preferably 2.3% by weight to 23% by weight, further preferably 2.3% by weight to 18% by weight, particularly preferably 2.5% by weight to 18% by weight, and most preferably 2.5% by weight to 16% by weight. If the content ratio of the polyfunctional isocyanate compound is within the above range, it is possible to provide a surface protective film that will not be easily peeled off from the adherend, representatively in the manufacturing process of the optical component and the electronic component, after being attached to the exposed surface of the optical component and the electronic component, and can be easily peeled off when peeling is required. In addition, if the content ratio of the polyfunctional isocyanate compound is within the above range, the haze can be reduced. In particular, if the haze can be reduced to less than 3%, the inspection of the surface protective film of the embodiment of the present invention is further improved.
[0156] In order to cure the composition containing a polyol and a polyfunctional isocyanate compound, a catalyst is preferably used. Examples of such catalysts include organometallic compounds, tertiary amine compounds, etc. The catalyst may be only one type or two or more types.
[0157] Examples of the organometallic compound include iron compounds, tin compounds, titanium compounds, zirconium compounds, lead compounds, cobalt compounds, zinc compounds, etc. Among these, iron compounds and tin compounds are preferred from the viewpoint of reaction rate and pot life of the adhesive layer.
[0158] Examples of the iron-based compound include iron acetylacetonate and iron 2-ethylhexanoate.
[0159] Examples of the tin compound include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin maleate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin sulfide, tributyltin methoxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, dioctyltin dilaurate, tributyltin chloride, tributyltin trichloroacetate, and 2-ethyltin hexanoate.
[0160] Examples of the titanium-based compound include dibutyltitanium dichloride, tetrabutyl titanate, and butoxytitanium trichloride.
[0161] Examples of the zirconium-based compound include zirconium naphthenate and zirconium acetylacetonate.
[0162] Examples of the lead compound include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate.
[0163] Examples of the cobalt-based compound include cobalt 2-ethylhexanoate and cobalt benzoate.
[0164] Examples of the zinc-based compound include zinc naphthenate and zinc 2-ethylhexanoate.
[0165] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undec-7-ene.
[0166] The amount of the catalyst is preferably 0.005 wt % to 1.00 wt %, more preferably 0.01 wt % to 0.75 wt %, further preferably 0.01 wt % to 0.50 wt %, and particularly preferably 0.01 wt % to 0.20 wt % relative to the polyol. If the amount of the catalyst is within the above range, a surface protection film can be provided which is not easily peeled off from an adherend, is not easily peeled off after being attached to the exposed surface of the optical component and the electronic component in the manufacturing process of the optical component and the electronic component, and can be easily peeled off when peeling is required.
[0167] In the composition containing polyol and polyfunctional isocyanate compound, any other appropriate components can be included within the range that does not impair the effect of the present invention. Such other components include, for example, antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking delay agents, inorganic fillers, organic fillers, metal powders, pigments, foils, softeners, antioxidants, conductive agents, surface lubricants, leveling agents, anticorrosives, heat stabilizers, polymerization inhibitors, lubricants, solvents, etc.
[0168] The preferred embodiment includes an anti-degradation agent such as an antioxidant, a UV absorber, and a light stabilizer among these other components. By making the adhesive composition include an anti-degradation agent, even if the adhesive layer formed after being attached to the adherend is stored in a heated state, the adherend is not easy to produce residual adhesive, etc., and the residual adhesive prevention property is excellent. The anti-degradation agent may be only one kind or may be two or more. As the anti-degradation agent, an antioxidant is particularly preferred.
[0169] Examples of the antioxidant include radical chain inhibitors and peroxide decomposers.
[0170] Examples of the radical chain inhibitor include phenolic antioxidants and amine antioxidants.
[0171] Examples of the peroxide decomposer include sulfur-based antioxidants and phosphorus-based antioxidants.
[0172] Examples of the phenolic antioxidant include monophenolic antioxidants, bisphenolic antioxidants, and polymeric phenolic antioxidants.
[0173] Examples of the monophenol antioxidant include 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, and stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0174] Examples of the bisphenol antioxidant include 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane.
[0175] Examples of the polymeric phenolic antioxidant include 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyric acid]diol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-s-triazine-2,4,6-(1H, 3H, 5H)trione, and tocopherol.
[0176] Examples of the sulfur-based antioxidant include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate.
[0177] Examples of the phosphorus-based antioxidant include triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite.
[0178] Examples of the ultraviolet absorber include benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers, salicylic acid ultraviolet absorbers, oxalic acid anilide ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, and triazine ultraviolet absorbers.
[0179] Examples of the benzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2,2'-dihydroxy-4-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and bis(2-methoxy-4-hydroxy-5-benzoylphenyl)methane.
[0180] Examples of the benzotriazole ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole. 5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octyloxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2'-hydroxy-5'-methacryloyloxyphenyl)-2H-benzotriazole, etc.
[0181] Examples of the salicylic acid-based ultraviolet absorber include phenyl salicylate, p-tert-butylphenyl salicylate, and p-octylphenyl salicylate.
[0182] Examples of the cyanoacrylate-based ultraviolet absorber include 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate and ethyl-2-cyano-3,3'-diphenylacrylate.
[0183] Examples of the light stabilizer include hindered amine light stabilizers and ultraviolet light stabilizers.
[0184] Examples of the hindered amine light stabilizer include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and (methyl-1,2,2,6,6-pentamethyl-4-piperidyl) sebacate.
[0185] Examples of the ultraviolet stabilizer include bis(octylphenyl)nickel sulfide, [2,2′-thiobis(4-tert-octylphenol)]-n-butylamine nickel, 3,5-di-tert-butyl-4-hydroxybenzyl phosphate monoethyl ester nickel complex, nickel dibutyldithiocarbamate, benzoate-type quenchers, and nickel dibutyldithiocarbamate.
[0186] [A-1-2-2. Urethane resin formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound]
[0187] The polyfunctional isocyanate compound may be used alone or in combination of two or more.
[0188] As the polyfunctional isocyanate compound, any appropriate polyfunctional isocyanate compound that can be used in the urethanization reaction can be adopted. Examples of such a polyfunctional isocyanate compound include the "polyfunctional isocyanate compound" described in the section A-1-2.
[0189] In the composition containing the urethane prepolymer and the polyfunctional isocyanate compound, any appropriate other components may be included within the range that does not impair the effect of the present invention. Such other components include, for example, antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking delay agents, inorganic fillers, organic fillers, metal powders, pigments, foils, softeners, antioxidants, conductive agents, surface lubricants, leveling agents, anticorrosives, heat stabilizers, polymerization inhibitors, lubricants, solvents, etc.
[0190] The mode of comprising the anti-degradation agent such as antioxidant, ultraviolet absorber, light stabilizer and the like among these other components is a preferred embodiment. By making the adhesive composition contain the anti-degradation agent, even if the adhesive layer formed is attached to the adherend and stored in a heated state, the adherend is not easy to produce residual adhesive, etc., and the residual adhesive prevention is excellent. The anti-degradation agent can be only one kind or two or more. As the anti-degradation agent, an antioxidant is particularly preferred. For details about the antioxidant, ultraviolet absorber, and light stabilizer, the description in item A-1-2-1 can be cited.
[0191] The equivalent ratio of the NCO group to the OH group of the urethane prepolymer and the polyfunctional isocyanate compound is preferably 5.0 or less, more preferably 0.01 to 3.0, more preferably 0.02 to 2.0, more preferably 0.03 to 2.0, more preferably 0.03 to 1.9, particularly preferably 0.05 to 1.9, and most preferably 0.05 to 1.8. If the equivalent ratio of the NCO group / OH group is within the above range, it is possible to provide a surface protective film that will not be easily peeled off from the adherend, representatively, in the manufacturing process of the optical component and the electronic component, after being attached to the exposed surface of the optical component and the electronic component, and can be easily peeled off when peeling is required. In addition, if the equivalent ratio of the NCO group / OH group is within the above range, the haze can be reduced. In particular, if the haze can be reduced to less than 3%, the inspection property of the surface protective film of the embodiment of the present invention is further improved.
[0192] Regarding the content ratio of the polyfunctional isocyanate compound, the polyfunctional isocyanate compound is preferably 0.01% by weight to 30% by weight relative to the urethane prepolymer, more preferably 0.05% by weight to 25% by weight, further preferably 0.1% by weight to 25% by weight, further preferably 0.5% by weight to 25% by weight, further preferably 0.5% by weight to 23% by weight, particularly preferably 1% by weight to 23% by weight, and most preferably 1% by weight to 21% by weight. If the content ratio of the polyfunctional isocyanate compound is within the above range, it is possible to provide a surface protective film that will not be easily peeled off from the adherend, representatively in the manufacturing process of the optical component and the electronic component, after being attached to the exposed surface of the optical component and the electronic component, and can be easily peeled off when peeling is required. In addition, if the content ratio of the polyfunctional isocyanate compound is within the above range, the haze can be reduced. In particular, if the haze can be reduced to less than 3%, the inspection of the surface protective film of the embodiment of the present invention is further improved.
[0193] <A-1-3. Ionic compounds>
[0194] As an ionic compound, any appropriate ionic compound can be adopted within the scope of not damaging the effect of the present invention. As such an ionic compound, an ionic liquid is preferred, and an ionic liquid comprising a fluorine organic anion is more preferably included. By making the adhesive composition include both an ionic compound and a fluorine-based compound described later in addition to the base polymer, the following surface protection film can be provided: comprising an adhesive layer and representatively in the manufacturing process of optical components and electronic components in order to prevent the surface damage of the optical components and the electronic components during processing, assembly, inspection, transportation, etc. and being attached to the exposed surface of the optical components and the electronic components, fully suppressing the peeling static voltage, and not damaging the optical components and the electronic components when peeling.
[0195] The ionic compound may be used alone or in combination of two or more.
[0196] The ionic liquid refers to a molten salt (ionic compound) that is liquid at 25°C.
[0197] As ionic liquid, any appropriate ionic liquid can be adopted within the scope of not damaging the effect of the present invention. As such ionic liquid, preferably an ionic liquid comprising fluorine organic anions, more preferably an ionic liquid consisting of fluorine organic anions and onium cations. By adopting an ionic liquid consisting of fluorine organic anions and onium cations as an ionic liquid, it is used in combination with the fluorine-based compound described later, so as to provide the following surface protection film: comprising an adhesive layer and representatively in the manufacturing process of optical components and electronic components in order to prevent the surface damage of the optical components and the electronic components during processing, assembly, inspection, transportation, etc., and being attached to the exposed surface of the optical components and the electronic components, more fully suppressing the peeling static voltage, and more not damaging the optical components and the electronic components when peeling.
[0198] As the onium cation that can constitute an ionic liquid, any appropriate onium cation can be adopted in the scope of not damaging the effect of the present invention.As such onium cation, it is preferably selected from at least one of nitrogen-containing onium cation, sulfur-containing onium cation, and phosphorus-containing onium cation.By selecting these onium cations, using in combination with the fluorine-based compound described later, it is possible to provide the following surface protection film: comprising an adhesive layer and representatively in the manufacturing process of optical components and electronic components in order to prevent the damage of the surface of the optical components and the electronic components during processing, assembly, inspection, transportation, etc. and being attached to the exposed surface of the optical components and the electronic components, more fully suppressing the stripping static voltage, and more not damaging the optical components and the electronic components when stripping.
[0199] As the onium cation capable of constituting the ionic liquid, at least one selected from cations having structures represented by general formulae (1) to (5) is preferred.
[0200]
[0201] In the general formula (1), Ra represents a hydrocarbon group having 4 to 20 carbon atoms, which may contain a hetero atom, and Rb and Rc are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a hetero atom. In the case where the nitrogen atom contains a double bond, Rc does not exist.
[0202] In the general formula (2), Rd represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a hetero atom, and Re, Rf, and Rg are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a hetero atom.
[0203] In the general formula (3), Rh represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a hetero atom; Ri, Rj, and Rk are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a hetero atom.
[0204] In the general formula (4), Z represents a nitrogen atom, a sulfur atom, or a phosphorus atom, and Rl, Rm, Rn, and Ro are the same or different and represent a hydrocarbon group having 1 to 20 carbon atoms, which may contain a hetero atom. When Z is a sulfur atom, Ro does not exist.
[0205] In the general formula (5), X represents a Li atom, a Na atom, or a K atom.
[0206] Examples of the cation represented by the general formula (1) include a pyridinium cation, a pyrrolidinium cation, a piperidinium cation, a cation having a pyrroline skeleton, and a cation having a pyrrole skeleton.
[0207] Specific examples of the cation represented by the general formula (1) include pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-butyl-3,4-dimethylpyridinium cation and 1,1-dimethylpyrrolidinium cation; 1-ethyl-1 -methylpyrrolidinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation, 1-ethyl-1-heptylpyrrolidinium cation, 1,1 pyrrolidinium cations such as 1-dipropylpyrrolidinium cation, 1-propyl-1-butylpyrrolidinium cation, 1,1-dibutylpyrrolidinium cation; 1-propylpiperidinium cation, 1-pentylpiperidinium cation, 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation; piperidinium cations such as 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, 1,1-dimethylpiperidinium cation, 1,1-dipropylpiperidinium cation, 1,1-dibutylpiperidinium cation; 2-methyl-1-pyrrolinium cation; 1-ethyl-2-phenylindolium cation; 1,2-dimethylindolium cation; 1-ethylcarbazole cation; etc.
[0208] Among these, from the viewpoint of being able to further express the effect of the present invention, preferably pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation are mentioned; 1-ethyl-1-methyl 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation , 1-ethyl-1-heptylpyrrolidinium cation and the like pyrrolidinium cation; 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1- Piperidinium cations such as pentylpiperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, etc.; more preferably 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-propylpiperidinium cation.
[0209] Examples of the cation represented by the general formula (2) include an imidazolium cation, a tetrahydropyrimidinium cation, and a dihydropyrimidinium cation.
[0210] Specific examples of the cation represented by the general formula (2) include imidazolium cations such as 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, 1,2-dimethyl-3-propylimidazolium cation, 1-ethyl-2,3-dimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, and 1-hexyl-2,3-dimethylimidazolium cation; and imidazolium cations such as 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1,3-dimethyl ... Tetrahydropyrimidinium cations such as 1,4,5,6-tetrahydropyrimidinium cation, 1,2,3-trimethyl-1,4,5,6-tetrahydropyrimidinium cation, 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation, 1,2,3,5-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation; 1,3-dimethyl-1,4-dihydropyrimidinium cation dihydropyrimidinium cations such as 1,3-dimethyl-1,6-dihydropyrimidinium cation, 1,2,3-trimethyl-1,4-dihydropyrimidinium cation, 1,2,3-trimethyl-1,6-dihydropyrimidinium cation, 1,2,3,4-tetramethyl-1,4-dihydropyrimidinium cation, and 1,2,3,4-tetramethyl-1,6-dihydropyrimidinium cation; etc.
[0211] Among these, from the viewpoint of being able to further express the effect of the present invention, imidazolium cations such as 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, and 1-tetradecyl-3-methylimidazolium cation are preferred, and 1-ethyl-3-methylimidazolium cation and 1-hexyl-3-methylimidazolium cation are more preferred.
[0212] Examples of the cation represented by the general formula (3) include a pyrazolium cation and a pyrazolinium cation.
[0213] Specific examples of the cation represented by the general formula (3) include pyrazolium cations such as 1-methylpyrazolium cation, 3-methylpyrazolium cation, 1-ethyl-2-methylpyrazolinium cation, 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation; pyrazolium cations such as 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation; and the like.
[0214] Examples of the cation represented by the general formula (4) include tetraalkylammonium cations, trialkylsulfonium cations, tetraalkylphosphonium cations, and cations in which a part of the alkyl groups mentioned above is substituted with an alkenyl group, an alkoxy group, or an epoxy group.
[0215] Specific examples of the cation represented by the general formula (4) include tetramethylammonium cation, tetraethylammonium cation, tetrabutylammonium cation, tetrapentylammonium cation, tetrahexylammonium cation, tetraheptylammonium cation, triethylmethylammonium cation, tributylethylammonium cation, trimethylpropylammonium cation, trimethyldecylammonium cation, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation, glycidyltrimethylammonium cation, trimethylsulfonium cation, triethylsulfonium cation, tributylsulfonium cation, trihexysulfonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, dimethyldecylammonium cation, tetramethylphosphonium cation, tetraethylphosphonium cation, tetrabutylphosphonium cation, tetrahexyphosphonium cation, tetraoctylphosphonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, trimethyldecylammonium cation, and diallyldimethylammonium cation.
[0216] Among these, from the viewpoint of being able to further express the effect of the present invention, preferably, asymmetric tetraalkylammonium cations, trialkylsulfonium cations, tetraalkylphosphonium cations such as triethylmethylammonium cation, tributylethylammonium cation, trimethyldecylammonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, dimethyldecylsulfonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, trimethyldecylphosphonium cation, and N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation, glycidyltrimethylammonium cation, diallyldimethylammonium cation, N,N-dimethylphosphonium cation, etc. are mentioned. Methyl-N-ethyl-N-propylammonium cation, N,N-dimethyl-N-ethyl-N-butylammonium cation, N,N-dimethyl-N-ethyl-N-pentylammonium cation, N,N-dimethyl-N-ethyl-N-hexylammonium cation, N,N-dimethyl-N-ethyl-N-heptylammonium cation, N,N-dimethyl-N-ethyl-N-nonylammonium cation, N,N-dimethyl-N,N-dipropylammonium cation, N,N-diethyl-N-propyl-N-butylammonium cation, N,N-dimethyl-N-propyl-N-pentylammonium cation, N,N-dimethyl-N-propyl-N-hexylammonium Cation, N,N-dimethyl-N-propyl-N-heptylammonium cation, N,N-dimethyl-N-butyl-N-hexylammonium cation, N,N-diethyl-N-butyl-N-heptylammonium cation, N,N-dimethyl-N-pentyl-N-hexylammonium cation, N,N-dimethyl-N,N-dihexylammonium cation, trimethylheptylammonium cation, N,N-diethyl-N-methyl-N-propylammonium cation, N,N-diethyl-N-methyl-N-pentylammonium cation, N,N-diethyl-N-methyl-N-heptylammonium cation, N,N-diethyl-N-propyl-N-pentylammonium cation , triethylpropylammonium cation, triethylpentylammonium cation, triethylheptylammonium cation, N,N-dipropyl-N-methyl-N-ethylammonium cation, N,N-dipropyl-N-methyl-N-pentylammonium cation, N,N-dipropyl-N-butyl-N-hexylammonium cation, N,N-dipropyl-N,N-dihexylammonium cation, N,N-dibutyl-N-methyl-N-pentylammonium cation, N,N-dibutyl-N-methyl-N-hexylammonium cation, trioctylmethylammonium cation, N-methyl-N-ethyl-N-propyl-N-pentylammonium cation, etc., and trimethylpropylammonium cation is more preferred.
[0217] As the fluorinated organic anion capable of constituting the ionic liquid, any appropriate fluorinated organic anion may be adopted within the range not impairing the effects of the present invention. Such fluorinated organic anion may be completely fluorinated (perfluorinated) or partially fluorinated.
[0218] Examples of such fluorinated organic anions include fluorinated arylsulfonates, perfluoroalkanesulfonates, bis(fluorosulfonyl)imides, bis(perfluoroalkanesulfonyl)imides, cyanoperfluoroalkanesulfonamides, bis(cyanoperfluoroalkanesulfonyl methides, cyano-bis-(perfluoroalkanesulfonyl)methides, tris(perfluoroalkanesulfonyl)methides, trifluoroacetates, perfluoroalkylates, tris(perfluoroalkanesulfonyl)methides, and (perfluoroalkanesulfonyl)trifluoroacetamide.
[0219] Among these fluorinated organic anions, perfluoroalkylsulfonates, bis(fluorosulfonyl)imides, and bis(perfluoroalkanesulfonyl)imides are more preferred, and more specifically, for example, trifluoromethanesulfonate, pentafluoroethanesulfonate, heptafluoropropanesulfonate, nonafluorobutanesulfonate, bis(fluorosulfonyl)imide, and bis(trifluoromethanesulfonyl)imide.
[0220] Specific examples of the ionic liquid may be appropriately selected from combinations of the above-mentioned cationic components and the above-mentioned anionic components and may be used. Specific examples of such ionic liquids include 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylpyridinium bis(pentafluoroethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1,1-dimethylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1- Ethylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, 1-methyl-1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-pentylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl 1-Hexylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-heptylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-pentylpyrrolidinium bis(trifluoromethanesulfonyl)imide )imide, 1-ethyl-1-hexylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-heptylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1,1-dipropylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-propyl-1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1,1-dibutylpyrrolidinium bis(trifluoromethanesulfonyl)imide 1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dimethylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-ethylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl 1-propylpiperidinium bis(fluorosulfonyl)imide, 1-methyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-hexylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-heptylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl -1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-hexylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-heptylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-Dipropylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-propyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dibutylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dimethylpyrrolidinium bis(pentafluoroethanesulfonyl)imide; 1-methyl-1-ethylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-pentylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-hexylpyrrolidinium 1-Methyl-1-heptylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-propylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-pentylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-hexylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-heptylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dipropylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-propyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dimethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-ethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dimethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-ethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-hexylpiperidinium bis(pentafluoroethanesulfonyl)imide 1-Methyl-1-heptylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-hexylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-heptylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dipropylpiperidinium bis(pentafluoroethanesulfonyl)imide; 1-propyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-Dibutylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-3-methylimidazolium trifluoroacetate, 1-ethyl-3-methylimidazolium heptafluorobutyrate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-ethyl-3-methylimidazolium nonafluorobutanesulfonate, 1-ethyl-3-methylimidazolium 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Ethyl-3-methylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium tris(trifluoromethanesulfonyl)methylate, 1-Butyl-3-methylimidazolium trifluoroacetate, 1-Butyl-3-methylimidazolium heptafluorobutyrate, -Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium perfluorobutanesulfonate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium trifluoromethanesulfonate, 1-hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide sulfonyl)imide, 1-ethyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1-propyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-2,3,5-trimethylpyrazolium bis(pentafluoroethanesulfonyl)imide, 1-propyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide 1-butyl-2,3,5-trimethylpyrazolium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-2,3,5-trimethylpyrazolium (trifluoromethanesulfonyl) trifluoroacetamide, 1-propyl-2,3,5-trimethylpyrazolium (trifluoromethanesulfonyl) trifluoroacetamide, 1-butyl-2,3,5-trimethylpyrazolium (trifluoromethanesulfonyl) trifluoroacetamide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-butylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide N,N-dimethyl-N-ethyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-nonylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N,N-dipropylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-butylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-butyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-pentyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N,N-dihexylammonium bis(trifluoromethanesulfonyl)imide, trimethylheptylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N,N-heptylammonium bis(trifluoromethanesulfonyl)imide, N, N-Diethyl-N-propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, triethylpropylammonium bis(trifluoromethanesulfonyl)imide, triethylpentylammonium bis(trifluoromethanesulfonyl)imide, triethylheptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dipropyl-N-methyl-N-ethylammonium bis(trifluoromethanesulfonyl)imide, N,N-dipropyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-dipropyl-N-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dipropyl-N,N-dihexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dibutyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide 、N,N-dibutyl-N-methyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, trioctylmethylammonium bis(trifluoromethanesulfonyl)imide, N-methyl-N-ethyl-N-propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, 1-butylpyridinium (trifluoromethanesulfonyl) trifluoroacetamide, 1-butyl-3-methylpyridinium (trifluoromethanesulfonyl) trifluoroacetamide, 1-ethyl-3-methylimidazolium (trifluoromethanesulfonyl) trifluoroacetamide, tetrahexylammonium bis(trifluoromethanesulfonyl)imide, diallyldimethylammonium trifluoromethanesulfonate, diallyldimethylammonium bis(trifluoromethanesulfonyl)imide, diallyldimethylammonium bis(pentafluoroethanesulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium trifluoromethanesulfonate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(pentafluoroethanesulfonyl)imide, glycidyl trimethylammonium trifluoromethanesulfonate, glycidyl trimethylammonium bis(trifluoromethanesulfonyl)imide, glycidyl trimethylammonium bis(pentafluoroethanesulfonyl)imide, diallyl dimethylammonium bis(trifluoromethanesulfonyl)imide, diallyl dimethyl bis(pentafluoroethanesulfonyl)imide, bis(trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium, etc.
[0221] Among these ionic liquids, 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyridin ... 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropane sulfonate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide.
[0222] Ionic liquids can use commercially available substances or can be synthesized as described below. As the synthesis method of ionic liquids, there is no particular limitation as long as the target ionic liquid can be obtained, and generally, a halide method, a hydroxide method, an acid ester method, a complex method, and a neutralization method as described in the document "Ionic Liquids - The Front Line and Future of Development" (published by CMC Group) can be used.
[0223] In the following, the synthesis methods of the halide method, hydroxide method, acid ester method, complex method and neutralization method are described by taking nitrogen-containing onium salt as an example, but other ionic liquids such as sulfur-containing onium salt and phosphorus-containing onium salt can also be obtained by the same method.
[0224] The halide method is a method performed by reactions such as those shown in reaction formulas (1) to (3). First, a tertiary amine is reacted with a halide alkane to obtain a halide (in reaction formula (1), chlorine, bromine or iodine is used as the halogen).
[0225] The obtained halide is reacted with an acid (HA) or a salt (MA, M is a cation such as ammonium, lithium, sodium, potassium, etc. that forms a salt with the target anion) having the target ionic liquid anion structure (A-) to obtain the target ionic liquid (R4NA).
[0226] (1)R3N+RX→R4NX(X: Cl, Br, I)
[0227] (2) R4NX+HA→R4NA+HX
[0228] (3)R4NX+MA→R4NA+MX (M: NH4, Li, Na, K, Ag, etc.)
[0229] The hydroxide method is a method performed by reactions such as those shown in reaction formulas (4) to (8). First, a halide (R4NX) is electrolyzed by an ion exchange membrane method (reaction formula (4)), by an OH-type ion exchange resin method (reaction formula (5)), or by a reaction with silver oxide (Ag2O) (reaction formula (6)) to obtain a hydroxide (R4NOH) (chlorine, bromine, or iodine is used as the halogen).
[0230] The obtained hydroxide is subjected to reactions of reaction formulas (7) to (8) in the same manner as in the above-mentioned halogenation method to obtain the target ionic liquid (R4NA).
[0231] (4)R4NX+H2O→R4NOH+1 / 2H2+1 / 2X z (X: Cl, Br, I)
[0232] (5) R4NX+P-OH→R4NOH+PX (P-OH: OH type ion exchange resin)
[0233] (6)R4NX+1 / 2Ag2O+1 / 2H2O→R4NOH+AgX
[0234] (7) R4NOH+HA→R4NA+H2O
[0235] (8)R4NOH+MA→R4NA+MOH (M: NH4, Li, Na, K, Ag, etc.)
[0236] The acid ester method is a method carried out by reactions such as those shown in reaction formulas (9) to (11). First, a tertiary amine (R3N) is reacted with an acid ester to obtain an acid ester (in reaction formula (9), as the acid ester, esters of inorganic acids such as sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, and carbonic acid, and esters of organic acids such as methanesulfonic acid, methylphosphonic acid, and formic acid are used).
[0237] The obtained acid ester is reacted by reaction formulas (10) to (11) in the same manner as the above-mentioned halogenation method to obtain the target ionic liquid (R4NA). In addition, an ionic liquid can also be directly obtained by using methyl trifluoromethanesulfonate, methyl trifluoroacetate, etc. as the acid ester.
[0238] (9) R3N+ROY→R4NOY
[0239] (OY: wait)
[0240] (10) R4NOY+HA→R4NA+HOY
[0241] (OY: In the case of )
[0242] (11)R4NOY+MA→R4NA+MOY (M: NH4, Li, Na, K, Ag, etc.)
[0243] The neutralization method is a method performed by a reaction as shown in reaction formula (12), and can be obtained by reacting a tertiary amine with an organic acid such as CF3COOH, CF3SO3H, (CF3SO2)2NH, (CF3SO2)3CH, or (C2F5SO2)2NH.
[0244] (12)R3N+HZ→R3NN + Z - [HZ: CF3COOH, CF3SO3H, (CF3SO2)2NH, (CF3SO2)3CH, (C2F5SO2)2NH and other organic acids]
[0245] In the above reaction formulae (1) to (12), R represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and may contain a hetero atom.
[0246] <A-1-4. Fluorine compounds>
[0247] As a fluorine compound, any appropriate fluorine compound can be used within the scope of not damaging the effect of the present invention. By making the adhesive composition include both the fluorine compound and the above-mentioned ionic compound in addition to the base polymer, the following surface protection film can be provided: comprising an adhesive layer and typically in the manufacturing process of optical components and electronic components, in order to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc., the optical component and the electronic component are attached to the exposed surface, the peeling static voltage is fully suppressed, and the optical component and the electronic component are not damaged during peeling.
[0248] The fluorine-based compound may be used alone or in combination of two or more.
[0249] Examples of the fluorine-based compound include at least one selected from fluorine-containing compounds, hydroxyl group-containing fluorine-based compounds, and crosslinkable functional group-containing fluorine-based compounds.
[0250] Examples of the fluorine-containing compound include compounds having a fluorinated aliphatic hydrocarbon skeleton, fluorinated organic compounds obtained by copolymerizing an organic compound with a fluorinated compound, fluorinated compounds containing an organic compound, etc. Examples of the fluorinated aliphatic hydrocarbon skeleton include fluorinated C1-C10 alkanes such as fluoromethane, fluoroethane, fluoropropane, fluoroisopropane, fluorobutane, fluoroisobutane, fluorotert-butane, fluoropentane, and fluorohexane.
[0251] The preferred embodiment of fluorinated compounds is an oligomer ("specific fluorinated compounds") having a fluorinated group and having a hydrophilic group and / or a lipophilic group. By including both (combination use) of an ionic compound and "specific fluorinated compounds" as described above, the effect of the present invention can be significantly expressed. It is inferred that the reason is that, as described above, by making the ionic compound and fluorinated compounds (preferably specific fluorinated compounds) that can express antistatic effect be present in the adhesive composition at the same time, the ionic compound is spread over the surface side (the side that adheres to the adherend) of the adhesive layer by the synergistic effect with the fluorinated compounds (preferably specific fluorinated compounds). As a fluorinated group, representative examples include fluorinated alkyl (such as CF3-, etc.) and / or fluorinated alkylene (such as -CF2-CF2-, etc.). A hydrophilic group is a group having hydrophilicity, which is translated into English as "hydrophilic", and is a property well known to those skilled in the art as "having affinity with water" (for example, see McGraw-Hill dictionary of scientific and technical terms (revised 3rd edition, Nikkan Kogyo Shimbun Co., Ltd.)). A lipophilic group is a group having lipophilicity, which is translated into English as "lipophilic", and is a property well known to those skilled in the art as "having affinity with oil" (for example, see McGraw-Hill dictionary of scientific and technical terms (revised 3rd edition, Nikkan Kogyo Shimbun Co., Ltd.)).
[0252] As the "specific fluorine-based compound", from the perspective of further expressing the effect of the present invention, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group is more preferably used. If the "specific fluorine-based compound" does not contain a hydrophilic group or the "specific fluorine-based compound" does not contain a lipophilic group, there is a risk that the effect of the present invention cannot be fully expressed.
[0253] From the perspective of further demonstrating the effects of the present invention, the preferred embodiment of the fluorine-containing compound is preferably a fluorine-containing compound having a surface tension of 26.0 mN / m to 27.0 mN / m when made into a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m). If the surface tension of the fluorine-containing compound when made into a 0.1% toluene solution is within the extremely narrow specific range of 26.0 mN / m to 27.0 mN / m, the effects of the present invention can be further demonstrated, especially the remarkable and unexpected effect of being able to fully suppress the peeling static voltage on the glass and the peeling static voltage on the resin. In particular, when it is envisioned that the surface protection film of the preferred embodiment of the present invention is used for a predetermined purpose, that is, the use of being attached to the exposed surface of an optical component and an electronic component, it is extremely important to be able to demonstrate the effect of being able to fully suppress the peeling static voltage on the glass and the peeling static voltage on the resin.
[0254] A particularly preferred embodiment of the fluorine-containing compound is an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and the surface tension when made into a 0.1% toluene solution is 26.0mN / m to 27.0mN / m (the surface tension of toluene is 27.9mN / m). If a particularly preferred embodiment of the fluorine-containing compound is an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and the surface tension when made into a 0.1% toluene solution is 26.0mN / m to 27.0mN / m (the surface tension of toluene is 27.9mN / m), the effect of the present invention can be further demonstrated, especially the extremely significant and unexpected effect of being able to fully suppress the peeling static voltage to the glass and the peeling static voltage to the resin. In particular, when it is assumed that the surface protection film of the preferred embodiment of the present invention is used for the intended purpose, that is, the use of being attached to the exposed surface of the optical component and the electronic component, it is extremely important to be able to fully suppress the peeling static voltage to the glass and the peeling static voltage to the resin.
[0255] As commercially available fluorine-containing compounds, for example, the following products are exemplified.
[0256] MEGAFACE series made by DIC Co., Ltd.:
[0257] Representative ones are "MEGAFACE F-114", "MEGAFACE F-251", "MEGAFACE F-253", "MEGAFACE F-281", "MEGAFACE F-410", "MEGAFACE F-430", "MEGAFACE F-444", "MEGAFACEF-477", "MEGAFACE F-510", "MEGAFACE F-551-A", "MEGAFACE F-553", "MEGAFACE F-554", "MEGAFACE F-555-A", "MEGAFACE F-556", "MEGAFACE F-557", "MEGAFACE F-558", "MEGAFACE F-559", "MEGAFACE F-560", "MEGAFACE F-561", "MEGAFACE F-562", "MEGAFACEF-563", "MEGAFACE F-565", "MEGAFACE F-568", "MEGAFACE F-569", "MEGAFACE F-570", "MEGAFACE F-576", "MEGAFACE R-01", "MEGAFACE R-40", "MEGAFACE R-40-LM", "MEGAFACER-41", "MEGAFACE R-41-LM", "MEGAFACE R-94", "MEGAFACE RS-56", "MEGAFACE RS-72-K", "MEGAFACE RS-75-A", "MEGAFACE RS-75-NS", "MEGAFACE RS-78", "MEGAFACE RS-90", etc.
[0258] Surflon series manufactured by AGC Seimi Chemical Co., Ltd.:
[0259] Representative examples include "S-242", "S-243", "S-386" and the like.
[0260] FC series manufactured by Sumitomo 3M Limited:
[0261] Representative examples include "FC-4430" and "FC-4432".
[0262] Ftergent series made by NEOS COMPANY LIMITED:
[0263] Representative examples include "Ftergent 100", "Ftergent 100C", "Ftergent 110", "Ftergent 150", "Ftergent 150CH", "Ftergent 250", and "Ftergent 400SW".
[0264] PF series manufactured by Kitamura Chemical Industry Co., Ltd.:
[0265] Representative ones are "PF-136A", "PF-156A", "PF-151N", "PF-636", "PF-6320", "PF-656", "PF-6520", "PF-651", "PF-652", "PF-3320" and the like.
[0266] As the hydroxyl-containing fluorine-based compound, for example, conventionally known resins can be used, and examples thereof include hydroxyl-containing fluororesins described in International Publication No. 94 / 06870 Pamphlet, Japanese Patent Laid-Open No. 8-12921 Gazette, Japanese Patent Laid-Open No. 10-72569 Gazette, Japanese Patent Laid-Open No. 4-275379 Gazette, International Publication No. 97 / 11130 Pamphlet, International Publication No. 96 / 26254 Pamphlet, etc. As other hydroxyl-containing fluororesins, examples thereof include fluoroolefin copolymers described in Japanese Patent Laid-Open No. 8-231919 Gazette, Japanese Patent Laid-Open No. 10-265731 Gazette, Japanese Patent Laid-Open No. 10-204374 Gazette, Japanese Patent Laid-Open No. 8-12922 Gazette, etc. In addition, copolymers of compounds having fluorinated alkyl groups in hydroxy-containing compounds, fluorinated organic compounds copolymerized with fluorinated compounds in hydroxy-containing compounds, fluorinated compounds containing hydroxy-containing organic compounds, etc. can be listed. As such hydroxy-containing fluorine-based compounds, for example, trade names "LUMIFLON" (made by Asahi Glass Co., Ltd.), trade name "Cefralcoat" (made by Central Glass Co., Ltd.), trade name "Zaflon" (made by Toa Synthetic Co., Ltd.), trade name "ZEFFLE" (made by DAIKIN INDUSTRIES, Ltd.), etc. can be listed as commercial products.
[0267] As fluorine compounds containing crosslinkable functional groups, for example, carboxylic acid compounds having fluorinated alkyl groups such as perfluorooctanoic acid, copolymers of compounds having fluorinated alkyl groups in compounds containing crosslinkable functional groups, fluorine-containing organic compounds copolymerized with fluorine-containing compounds in compounds containing crosslinkable functional groups, fluorine-containing compounds containing compounds containing crosslinkable functional groups, etc. As such fluorine compounds containing crosslinkable functional groups, for example, trade names "MEGAFACE F-570", "MEGAFACE RS-55", "MEGAFACE RS-56", "MEGAFACE RS-72-K", "MEGAFACE RS-75", "MEGAFACE RS-76-E", "MEGAFACE RS-76-NS", "MEGAFACE RS-78", "MEGAFACE RS-90" (manufactured by DIC Corporation) and the like can be cited as commercial products.
[0268] Among the fluorine-containing compounds available in the form of commercial products, products corresponding to the above-mentioned "oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group" include, for example,
[0269] "MEGAFACE F-477" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0270] "MEGAFACE F-551-A" (fluorine-containing and lipophilic oligomer, surface tension of 0.1% toluene solution = 25.6 mN / m),
[0271] "MEGAFACE F-553" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0272] "MEGAFACE F-554" (fluorine-containing and lipophilic oligomer, surface tension of 0.1% toluene solution = 25.0 mN / m),
[0273] "MEGAFACE F-555-A" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 20.4 mN / m when made into a 0.1% toluene solution),
[0274] "MEGAFACE F-557" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.3 mN / m when made into a 0.1% toluene solution),
[0275] "MEGAFACE F-559" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.1 mN / m when made into a 0.1% toluene solution),
[0276] "MEGAFACE F-563" (fluorine-containing and lipophilic oligomer, surface tension of 0.1% toluene solution = 20.2 mN / m),
[0277] "MEGAFACE F-569" (an oligomer containing a fluorine-containing group and a hydrophilic group, with a surface tension of 19.7 mN / m when made into a 0.1% toluene solution); etc.
[0278] Among the fluorinated compounds available in the form of commercial products, products corresponding to the above-mentioned "fluorinated compound which is an oligomer containing a fluorinated group, a hydrophilic group, and a lipophilic group and has a surface tension of 26.0 mN / m to 27.0 mN / m (the surface tension of toluene is 27.9 mN / m) when it is made into a 0.1% toluene solution" include, representatively, DIC Corporation's
[0279] "MEGAFACE F-477" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0280] "MEGAFACE F-553" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0281] "MEGAFACE F-557" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, with a surface tension of 26.3 mN / m when made into a 0.1% toluene solution),
[0282] "MEGAFACE F-559" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and having a surface tension of 26.1 mN / m when made into a 0.1% toluene solution); etc.
[0283] <A-1-5. Other ingredients>
[0284] The adhesive composition may contain any appropriate other components within the scope of not impairing the effect of the present invention. As such other components, for example, resin components, crosslinking accelerators, crosslinking catalysts, silane coupling agents, silicone additives such as modified silicone oils, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, conductive agents, stabilizers, surface lubricants, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc. can be listed.
[0285] In the adhesive composition, modified silicone oil can be typically included as other components within the range that does not impair the effect of the present invention. By making the adhesive composition include modified silicone oil, the effect of antistatic properties can be exhibited. In particular, by using it in combination with an ionic liquid, the effect of antistatic properties can be further effectively exhibited.
[0286] When the adhesive composition includes modified silicone oil, the content ratio is preferably 0.001 to 50 parts by weight, more preferably 0.005 to 40 parts by weight, further preferably 0.007 to 30 parts by weight, particularly preferably 0.008 to 20 parts by weight, and most preferably 0.01 to 10 parts by weight relative to 100 parts by weight of the base polymer. By adjusting the content ratio of the modified silicone oil to the above range, the effect of the antistatic property can be further effectively demonstrated.
[0287] As the modified silicone oil, any appropriate modified silicone oil can be adopted within the range not impairing the effects of the present invention. Examples of such modified silicone oils include modified silicone oils available from Shin-Etsu Chemical Co., Ltd.
[0288] As the modified silicone oil, polyether-modified silicone oil is preferred. By using polyether-modified silicone oil, the antistatic property effect can be more effectively exhibited.
[0289] Examples of the polyether-modified silicone oil include side chain-type polyether-modified silicone oils, dual-end polyether-modified silicone oils, etc. Among these, dual-end polyether-modified silicone oils are preferred from the viewpoint of being able to fully and effectively exhibit the effect of antistatic properties.
[0290] 《A-2. Base material layer》
[0291] The substrate layer may be only one layer or may be two or more layers. The substrate layer may be a stretched substrate.
[0292] The thickness of the substrate layer is preferably 4 μm to 450 μm, more preferably 8 μm to 400 μm, further preferably 12 μm to 350 μm, and particularly preferably 16 μm to 250 μm.
[0293] For the surface of the substrate layer without the adhesive layer attached, in order to form a roll that is easy to unwind, for example, fatty acid amide, polyethyleneimine, long-chain alkyl additives, etc. can be added to the substrate layer to perform a demolding treatment, or a coating containing any appropriate release agent such as silicone, long-chain alkyl, fluorine, etc. can be provided.
[0294] As the material of the substrate layer, any appropriate material can be used according to the application. For example, plastic, paper, metal film, non-woven fabric, etc. can be mentioned. Plastic is preferred. That is, the substrate layer is preferably a plastic film. The substrate layer can be composed of one material or two or more materials. For example, it can be composed of two or more plastics.
[0295] Examples of the above-mentioned plastics include polyester resins, polyamide resins, and polyolefin resins. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Examples of polyolefin resins include homopolymers of polypropylene; propylene copolymers of block, random, and graft systems using ethylene as a copolymer component; Reactor TPO; ethylene polymers of low density, high density, linear low density, and ultra-low density; ethylene copolymers such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers; and the like.
[0296] The substrate layer may contain any appropriate additives as required. Examples of additives that may be contained in the substrate layer include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, pigments, etc. The type, number, and content of the additives that may be contained in the substrate layer may be appropriately set according to the purpose. In particular, when the material of the substrate layer is plastic, it is preferred to contain several of the above-mentioned additives for the purpose of preventing deterioration. From the viewpoint of improving weather resistance, antioxidants, ultraviolet absorbers, light stabilizers, and fillers are particularly preferred as additives.
[0297] As the antioxidant, any appropriate antioxidant can be used. As such an antioxidant, for example, phenolic antioxidants, phosphorus-based processing heat stabilizers, lactone-based processing heat stabilizers, sulfur-based heat stabilizers, phenol-phosphorus antioxidants, etc. can be cited. The content ratio of the antioxidant is preferably 1% by weight or less, more preferably 0.5% by weight or less, and further preferably 0.01% by weight to 0.2% by weight relative to the base resin of the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0298] As the ultraviolet absorber, any appropriate ultraviolet absorber can be used. As such ultraviolet absorbers, for example, benzotriazole ultraviolet absorbers, triazine ultraviolet absorbers, benzophenone ultraviolet absorbers, etc. can be cited. The content ratio of the ultraviolet absorber is preferably 2% by weight or less, more preferably 1% by weight or less, and further preferably 0.01% by weight to 0.5% by weight relative to the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0299] As the light stabilizer, any appropriate light stabilizer can be used. Examples of such light stabilizers include hindered amine light stabilizers and benzoate light stabilizers. The light stabilizer content is preferably 2% by weight or less, more preferably 1% by weight or less, and further preferably 0.01% to 0.5% by weight, relative to the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0300] As a filler, any appropriate filler can be used. As such a filler, for example, an inorganic filler can be cited. As an inorganic filler, specifically, for example, carbon black, titanium oxide, zinc oxide, etc. can be cited. Regarding the proportion of the filler, relative to the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin), it is preferably 20% by weight or less, more preferably 10% by weight or less, and further preferably 0.01% by weight to 10% by weight.
[0301] Furthermore, as additives, for the purpose of imparting antistatic properties, inorganic, low molecular weight and high molecular weight antistatic agents such as surfactants, inorganic salts, polyols, metal compounds and carbon may also be preferably cited. In particular, high molecular weight antistatic agents and carbon are preferred from the viewpoints of preventing contamination and maintaining adhesion.
[0302] 《《B. Purpose》》
[0303] The surface protection film of the embodiment of the present invention is a surface protection film that includes an adhesive layer and is typically attached to the exposed surface of the optical component and the electronic component in order to prevent damage to the surface of the optical component and the electronic component during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical component and the electronic component, and can fully suppress the peeling static voltage and will not damage the optical component and the electronic component when peeling. Therefore, it can be suitably used for the surface protection of optical components and electronic components. The optical component of the present invention is attached with the surface protection film of the present invention. The electronic component of the present invention is attached with the surface protection film of the present invention.
[0304] Example
[0305] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples in any way. It should be noted that the test and evaluation methods in the examples are as follows. It should be noted that when "parts" are recorded, they refer to "parts by weight" unless otherwise stated, and when "%" is recorded, they refer to "% by weight" unless otherwise stated.
[0306] <Measurement of Surface Free Energy of Adhesive Layer Surface with Respect to Diiodomethane>
[0307] The surface protection film from which the separator was peeled off was cut into a size of 50 mm in width and 100 mm in length, and the adhesive layer surface was set as the upper surface and fixed to a contact angle meter (made by Kyowa Interface Science Co., Ltd., model "CA-X"), and 2.0 μL of water was dripped onto the adhesive layer surface to measure the contact angle. Then, 2.0 μL of diiodomethane was dripped through the same steps to measure the contact angle. The surface free energy of the adhesive layer surface relative to diiodomethane was calculated using the Owens-Wendt method from the contact angle values of the above two liquids.
[0308] <Measurement of peeling force from glass plate (after standing at 23°C for 30 minutes)>
[0309] The adhesive layer side of the surface protection film (25 mm width×140 mm length) from which the separator was peeled was bonded to a glass plate (soda lime glass, manufactured by Matsunami Glass Industries, Ltd.) by reciprocating once with a 2 kg hand roller and left to stand at an ambient temperature of 23° C. for 30 minutes.
[0310] The evaluation sample obtained as described above is measured using a tensile testing machine. As a tensile testing machine, the trade name "Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NXplus)" manufactured by Shimadzu Corporation is used. The evaluation sample is set in the tensile testing machine and the tensile test is started. Specifically, the load when the surface protection film is peeled off from the above-mentioned glass plate is measured, and the average load at this time is set as the peeling force of the surface protection film from the glass plate. The conditions of the tensile test are set as test environment temperature: 23°C, peeling angle: 180 degrees, peeling speed (tensile speed): 300mm / min.
[0311] <Measurement of electrostatic peeling voltage against glass and acrylic plate>
[0312] The surface protection film from which the insulator has been peeled off is cut into a size of 70 mm in width and 100 mm in length, and is pressed onto the surface of glass (soda-lime glass, manufactured by Matsunami Glass Industries, Ltd.) or acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a hand roller so that one end of the surface protection film protrudes 30 mm from the end of the glass.
[0313] After the sample is placed in an environment of 23°C × 50% RH for 1 day, it is set at a specified position on a sample fixing table with a height of 20 mm. The end of the surface protection film protruding 30 mm from the glass is fixed to an automatic winder and peeled at a peeling angle of 150° and a peeling speed of 30 m / min. The potential on the surface of the adherend generated at this time is measured using a potential measuring device (SHISHIDO ELECTROSTATIC, LTD., model "STATIRON DZ-4") fixed at a position 30 mm high from the center of the adherend as the peeling static voltage for the glass or the peeling static voltage for the acrylic plate. The measurement is carried out in an environment of 23°C and 50% RH.
[0314] <Measurement of residual adhesive strength to glass>
[0315] A surface protective film was laminated on the entire surface of a glass plate (manufactured by Matsunami Glass, 1.35 mm × 10 cm × 10 cm) using a hand roller, and after being stored in an atmosphere of temperature 23°C and humidity 55% RH for 24 hours, the surface protective film was peeled off at a speed of 0.3 m / min, and a No. 31B tape (manufactured by Nitto Denko Corporation, substrate thickness: 25 μm) cut into a length of 150 mm and a width of 19 mm was laminated using a 2.0 kg roller back and forth once in an atmosphere of temperature 23°C and humidity 55% RH. After aging for 30 minutes in an atmosphere of temperature 23°C and humidity 55% RH, the adhesive strength was measured by peeling at a peeling angle of 180 degrees and a tensile speed of 300 mm / min using a tensile tester (trade name "Autograph AG-XplusHS 6000 mm / min high speed mode (AG-50NX plus)" manufactured by Shimadzu Corporation).
[0316] Separately, the adhesive strength of the No. 31B tape having a width of 19 mm was measured in the same manner on a glass plate that had not been subjected to the above treatment, and the residual adhesive ratio was calculated by the following formula.
[0317] Residual adhesion rate (%) = (Adhesion of No. 31B to the glass plate after peeling off the surface protection film / Adhesion of No. 31B to the glass plate) × 100
[0318] The residual adhesion rate to glass is an indicator of the extent to which the adhesive component of the surface protection film is transferred to and contaminates the surface of the adherend. The higher the residual adhesion rate to glass, the greater the concern of the surface protection film to contaminate the adherend, and the lower the residual adhesion rate to glass, the less the concern of the surface protection film to contaminate the adherend.
[0319] <Measurement of haze>
[0320] According to the conditions described in the following examples and comparative examples, the adhesive solution obtained in the following examples and comparative examples was applied to the release-treated surface of a 75 μm thick polyester film (trade name: Diafoil MRF75, manufactured by Mitsubishi Chemical Corporation) with a release treatment on one side with silicone and dried to prepare an adhesive layer. Next, a 75 μm thick polyester film (trade name: Diafoil MRE75, manufactured by Mitsubishi Chemical Corporation) with a release treatment on one side with silicone was covered on the surface of the adhesive layer so that the release-treated surface of the film became the adhesive layer side, and aged for 5 days at room temperature. Prepare 2 sheets of 50 mm × 50 mm thick paper with a 20 mm × 20 mm hole in the center, and paste the sample itself on one sheet of paper by moving a hand roller back and forth once, and then paste another sheet of paper. The evaluation sample obtained as described above was measured using "HM-150N" manufactured by Murakami Color Technology Research Institute.
[0321] <Description of fluorine-containing compounds used in Examples and Comparative Examples>
[0322] As the fluorine-containing compound, the fluorine-containing compounds used in Examples and Comparative Examples are as follows.
[0323] "MEGAFACE F-477" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0324] "MEGAFACE F-551-A" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group and a lipophilic group, surface tension of 25.6 mN / m when made into a 0.1% toluene solution),
[0325] "MEGAFACE F-553" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension of 26.4 mN / m when made into a 0.1% toluene solution),
[0326] "MEGAFACE F-554" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group and a lipophilic group, surface tension of 25.0 mN / m when made into a 0.1% toluene solution),
[0327] "MEGAFACE F-555-A" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension of 20.4 mN / m when made into a 0.1% toluene solution),
[0328] "MEGAFACE F-557" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension of 26.3 mN / m when made into a 0.1% toluene solution),
[0329] "MEGAFACE F-559" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension of 26.1 mN / m when made into a 0.1% toluene solution),
[0330] "MEGAFACE F-563" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group and a lipophilic group, surface tension of 20.2 mN / m when made into a 0.1% toluene solution),
[0331] "MEGAFACE F-569" (manufactured by DIC Corporation, an oligomer containing a fluorine-containing group and a hydrophilic group, surface tension of 19.7 mN / m when made into a 0.1% toluene solution),
[0332] [Example 1]
[0333] 85 parts by weight of PREMINOL (manufactured by Asahi Glass Co., Ltd., Mn=10000) which is a polyol having three hydroxyl groups, 13 parts by weight of SANNIX GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) which is a polyol having three hydroxyl groups, 2 parts by weight of SANNIX GP1000 (manufactured by Sanyo Chemical Co., Ltd., Mn=1000) which is a polyol having three hydroxyl groups, 18 parts by weight of an isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) which is a crosslinking agent, 0.02 parts by weight of iron acetylacetonate (manufactured by Nippon Chemical Industry Co., Ltd.) which is a catalyst, and MEGAFACE which is a fluorine-based oligomer were prepared. 1 part by weight of F-553 (manufactured by DIC Corporation) and 1 part by weight of 1-ethyl-3-methylimidazolium tri(fluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound were diluted with ethyl acetate so that the total solid content reached 35% by weight, thereby obtaining a carbamate adhesive solution. The carbamate adhesive solution was then applied to a substrate composed of a polyester resin (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying reached 20 μm, and cured and dried under the conditions of a drying temperature of 130°C and a drying time of 2 minutes. Next, a release sheet composed of a polyester resin with a thickness of 25 μm and a silicone treatment applied to one side (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) was attached to the surface of the obtained adhesive layer, and the surface protective film (1) was obtained. Aging was performed at room temperature for 5 days and evaluation was performed. The release sheet was peeled off immediately before the evaluation. The results are shown in Table 1.
[0334] [Example 2]
[0335] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (2) to obtain a surface protection film (2), except that the fluorine-based oligomer (trade name "F-569", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content. The results are shown in Table 1.
[0336] [Example 3]
[0337] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-554", manufactured by DIC) was changed to 1 part by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (3) to obtain a surface protection film (3). The results are shown in Table 1.
[0338] [Example 4]
[0339] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (4) to obtain a surface protection film (4). The results are shown in Table 1.
[0340] [Example 5]
[0341] As shown in Table 1, a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive composition (5) was prepared in the same manner as in Example 1, except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110", manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.5 parts by weight in terms of solid content. A surface protection film (5) was obtained. The results are shown in Table 1.
[0342] [Example 6]
[0343] As shown in Table 1, a PSA layer composed of the PSA composition (6) was prepared in the same manner as in Example 1, except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110", manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.25 parts by weight in terms of solid content, thereby obtaining a surface protection film (6). The results are shown in Table 1.
[0344] [Example 7]
[0345] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-555-A", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (7) to obtain a surface protection film (7). The results are shown in Table 1.
[0346] [Example 8]
[0347] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (8) to obtain a surface protection film (8), except that the fluorine-based oligomer (trade name "F-559", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content. The results are shown in Table 1.
[0348] [Example 9]
[0349] As shown in Table 1, a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition (9) was prepared in the same manner as in Example 1 except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 1 part by weight in terms of solid content, thereby obtaining a surface protection film (9). The results are shown in Table 1.
[0350] [Example 10]
[0351] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-554", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (10) to obtain a surface protection film (10). The results are shown in Table 1.
[0352] [Example 11]
[0353] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (11) to obtain a surface protection film (11). The results are shown in Table 1.
[0354] [Example 12]
[0355] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (12) to obtain a surface protection film (12). The results are shown in Table 1.
[0356] [Example 13]
[0357] As shown in Table 1, a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive composition (13) was prepared in the same manner as in Example 1, except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110", manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.5 parts by weight. A surface protection film (13) was obtained. The results are shown in Table 1.
[0358] [Example 14]
[0359] As shown in Table 1, a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive composition (14) was prepared in the same manner as in Example 1, except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110", manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.25 parts by weight. A surface protection film (14) was obtained. The results are shown in Table 1.
[0360] [Example 15]
[0361] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-551-A", manufactured by DIC) was changed to 1 part by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (15) to obtain a surface protection film (15). The results are shown in Table 1.
[0362] [Example 16]
[0363] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-556", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (16) to obtain a surface protection film (16). The results are shown in Table 1.
[0364] [Example 17]
[0365] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-551-A", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (17) to obtain a surface protection film (17). The results are shown in Table 1.
[0366] [Example 18]
[0367] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-554", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (18) to obtain a surface protection film (18). The results are shown in Table 1.
[0368] [Example 19]
[0369] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-563", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (19) to obtain a surface protection film (19). The results are shown in Table 1.
[0370] [Example 20]
[0371] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (20) to obtain a surface protection film (20). The results are shown in Table 1.
[0372] [Example 21]
[0373] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 2.0 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (21) to obtain a surface protection film (21). The results are shown in Table 1.
[0374] [Example 22]
[0375] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (22) to obtain a surface protection film (22), except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 4.0 parts by weight in terms of solid content. The results are shown in Table 1.
[0376] [Example 23]
[0377] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 6.0 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (23) to obtain a surface protection film (23). The results are shown in Table 1.
[0378] [Example 24]
[0379] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (24) to obtain a surface protection film (24), except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 2.0 parts by weight in terms of solid content. The results are shown in Table 1.
[0380] [Example 25]
[0381] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (25) to obtain a surface protection film (25), except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 4.0 parts by weight in terms of solid content. The results are shown in Table 1.
[0382] [Example 26]
[0383] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 6.0 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (26) to obtain a surface protection film (26). The results are shown in Table 1.
[0384] [Example 27]
[0385] As shown in Table 1, the same procedure as in Example 4 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 15.9 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (27) to obtain a surface protection film (27). The results are shown in Table 1.
[0386] [Example 28]
[0387] As shown in Table 1, the same procedure as in Example 4 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 14.1 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (28) to obtain a surface protection film (28). The results are shown in Table 1.
[0388] [Example 29]
[0389] As shown in Table 1, the same procedure as in Example 4 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 12.4 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (29) to obtain a surface protection film (29). The results are shown in Table 1.
[0390] [Example 30]
[0391] As shown in Table 1, the same procedure as in Example 4 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 10.6 parts by weight in terms of solid content, thereby producing an adhesive layer formed of the adhesive composition (30) to obtain a surface protection film (30). The results are shown in Table 1.
[0392] [Example 31]
[0393] As shown in Table 1, the same procedure as in Example 4 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 8.8 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (31) to obtain a surface protection film (31). The results are shown in Table 1.
[0394] [Example 32]
[0395] As shown in Table 1, the same procedure as in Example 12 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 15.9 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (32) to obtain a surface protection film (32). The results are shown in Table 1.
[0396] [Example 33]
[0397] As shown in Table 1, the same procedure as in Example 12 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 14.1 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (33) to obtain a surface protection film (33). The results are shown in Table 1.
[0398] [Example 34]
[0399] As shown in Table 1, the same procedure as in Example 12 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 12.4 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (34) to obtain a surface protection film (34). The results are shown in Table 1.
[0400] [Example 35]
[0401] As shown in Table 1, the same procedure as in Example 12 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 10.6 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (35) to obtain a surface protection film (35). The results are shown in Table 1.
[0402] [Example 36]
[0403] As shown in Table 1, the same procedure as in Example 12 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 8.8 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (36) to obtain a surface protection film (36). The results are shown in Table 1.
[0404] [Example 37]
[0405] As shown in Table 1, the same method as in Example 4 was used to prepare an adhesive layer formed from the adhesive composition (37) to obtain a surface protection film (37), except that the fluorine-based oligomer (trade name "F-557", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content. The results are shown in Table 1.
[0406] [Example 38]
[0407] As shown in Table 1, the same procedure as in Example 37 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 15.9 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (38) to obtain a surface protection film (38). The results are shown in Table 1.
[0408] [Example 39]
[0409] As shown in Table 1, the same procedure as in Example 37 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 14.1 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (39) to obtain a surface protection film (39). The results are shown in Table 1.
[0410] [Example 40]
[0411] As shown in Table 1, the same procedure as in Example 37 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 12.4 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (40) to obtain a surface protection film (40). The results are shown in Table 1.
[0412] [Example 41]
[0413] As shown in Table 1, the same procedure as in Example 37 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 10.6 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (41) to obtain a surface protection film (41). The results are shown in Table 1.
[0414] [Example 42]
[0415] As shown in Table 1, the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 8.8 parts by weight in terms of solid content, and the same procedure as in Example 37 was followed to produce an adhesive layer composed of the adhesive composition (42) to obtain a surface protection film (42). The results are shown in Table 1.
[0416] [Example 43]
[0417] As shown in Table 1, the same procedure as in Example 8 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 15.9 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (43) to obtain a surface protection film (43). The results are shown in Table 1.
[0418] [Example 44]
[0419] As shown in Table 1, the same procedure as in Example 8 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 14.1 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (44) to obtain a surface protection film (44). The results are shown in Table 1.
[0420] [Example 45]
[0421] As shown in Table 1, the same procedure as in Example 8 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 12.4 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (45) to obtain a surface protection film (45). The results are shown in Table 1.
[0422] [Example 46]
[0423] As shown in Table 1, the same procedure as in Example 8 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 10.6 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (46) to obtain a surface protection film (46). The results are shown in Table 1.
[0424] [Example 47]
[0425] As shown in Table 1, the same procedure as in Example 8 was carried out except that the isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) was changed to 8.8 parts by weight in terms of solid content, thereby producing an adhesive layer composed of the adhesive composition (47) to obtain a surface protection film (47). The results are shown in Table 1.
[0426] [Example 48]
[0427] 100 parts by weight of urethane prepolymer A, 3 parts by weight of isocyanate compound (Coronate HX: C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, 1 part by weight of fluorine-based oligomer MEGAFACE F-553 (manufactured by DIC Corporation), and 1 part by weight of 1-ethyl-3-methylimidazolium tri(fluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound were diluted with ethyl acetate so that the total solid content was 49% by weight to obtain a urethane adhesive solution. Then, the urethane adhesive solution was applied to a substrate made of a polyester resin (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying was 75 μm, and cured and dried under the conditions of a drying temperature of 120° C. and a drying time of 3 minutes to prepare an adhesive layer composed of an adhesive composition (48). Next, a silicone-treated surface of a release sheet made of polyester resin (trade name "MRF25", 25 μm thick, manufactured by Mitsubishi Chemical Corporation) with one side subjected to silicone treatment was attached to the surface of the obtained adhesive layer to obtain a surface protection film (48). The film was aged for 5 days at room temperature and evaluated. The release sheet was peeled off immediately before the evaluation. The results are shown in Table 1.
[0428] [Example 49]
[0429] As shown in Table 1, the same method as in Example 48 was used except that the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 1.0 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (49) to obtain a surface protection film (49). The results are shown in Table 1.
[0430] [Example 50]
[0431] As shown in Table 1, the same method as in Example 48 was used except that the fluorine-based oligomer (trade name "F-557", manufactured by DIC) was changed to 1.0 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (50) to obtain a surface protection film (50). The results are shown in Table 1.
[0432] [Example 51]
[0433] As shown in Table 1, the same method as in Example 48 was used to prepare an adhesive layer formed from the adhesive composition (51) to obtain a surface protection film (51), except that the fluorine-based oligomer (trade name "F-559", manufactured by DIC) was changed to 1.0 parts by weight in terms of solid content. The results are shown in Table 1.
[0434] [Comparative Example 1]
[0435] As shown in Table 1, the fluorine-based oligomer (trade name "F-569", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) was not used. The same procedures as in Example 1 were followed to produce an adhesive layer composed of the adhesive composition (C1) to obtain a surface protection film (C1). The results are shown in Table 1.
[0436] [Comparative Example 2]
[0437] As shown in Table 1, the fluorine-based oligomer (trade name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) was not used. The same procedures as in Example 1 were followed to produce an adhesive layer composed of the adhesive composition (C2) to obtain a surface protection film (C2). The results are shown in Table 1.
[0438] [Comparative Example 3]
[0439] As shown in Table 1, the fluorine-based oligomer (trade name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) was not used. The same procedures as in Example 1 were followed to produce an adhesive layer composed of the adhesive composition (C3) to obtain a surface protection film (C3). The results are shown in Table 1.
[0440] [Comparative Example 4]
[0441] As shown in Table 1, the fluorine-based oligomer (trade name "F-551-A", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) was not used. The same procedures as in Example 1 were performed to produce an adhesive layer composed of the adhesive composition (C4) to obtain a surface protection film (C4). The results are shown in Table 1.
[0442] [Comparative Example 5]
[0443] As shown in Table 1, the same method as in Example 1 was used to prepare an adhesive layer formed from the adhesive composition (C5) to obtain a surface protection film (C5), except that the fluorine-based oligomer (trade name "F-571", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content. The results are shown in Table 1.
[0444] [Comparative Example 6]
[0445] As shown in Table 1, the same method as in Example 1 was used except that the fluorine-based oligomer (trade name "F-552", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (C6) to obtain a surface protection film (C6). The results are shown in Table 1.
[0446] [Comparative Example 7]
[0447] As shown in Table 1, a PSA layer composed of the PSA composition (C7) was prepared in the same manner as in Example 1 except that the fluorinated oligomer was not used, thereby obtaining a surface protection film (C7).
[0448] [Comparative Example 8]
[0449] As shown in Table 1, a PSA layer composed of the PSA composition (C8) was prepared in the same manner as in Example 1, except that no fluorine-based oligomer and no ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) were used, thereby obtaining a surface protection film (C8). The results are shown in Table 1.
[0450] [Comparative Example 9]
[0451] As shown in Table 1, a PSA layer formed from the PSA composition (C9) was prepared in the same manner as in Example 48, except that no fluorine-based oligomer was used and no ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) was used, thereby obtaining a surface protection film (C9). The results are shown in Table 1.
[0452] [Comparative Example 10]
[0453] As shown in Table 1, a PSA layer formed from the PSA composition (C10) was prepared in the same manner as in Example 49, except that no fluorine-based oligomer and no ionic compound (trade name "AS110, manufactured by Daiichi Kogyo Seiyaku) were used, thereby obtaining a surface protection film (C10). The results are shown in Table 1.
[0454] [Comparative Example 11]
[0455] As shown in Table 1, the same method as in Example 48 was used except that the fluorine-based oligomer (trade name "F-571", manufactured by DIC) was changed to 1 part by weight in terms of solid content, thereby producing an adhesive layer formed from the adhesive composition (C11) to obtain a surface protection film (C11). The results are shown in Table 1.
[0456] [Table 1]
[0457]
[0458] [Examples 52 to 103]
[0459] The separators of the surface protection films (1) to (51) obtained in Examples 1 to 51 were peeled off and the adhesive layer side was bonded to a polarizing plate (manufactured by Nitto Denko Corporation, trade name "TEG1465DUHC") as an optical member to obtain an optical member bonded with a surface protection film.
[0460] [Examples 104 to 155]
[0461] For the surface protection films (1) to (51) obtained in Examples 1 to 51, the separators were peeled off respectively, and the adhesive layer side was bonded to a conductive film (manufactured by Nitto Denko Corporation, trade name "ELECRYSTAV270L-TFMP") as an electronic component to obtain an electronic component bonded with a surface protection film.
[0462] Industrial Applicability
[0463] The surface protection film of the present invention can be used for any appropriate purpose. Preferably, the surface protection film of the present invention is used in the field of optical components and the field of electronic components.
Claims
1. A surface protection film comprising an adhesive layer, The adhesive constituting the adhesive layer is formed of an adhesive composition. The adhesive composition comprises a base polymer, a multifunctional isocyanate, an ionic compound, and a fluorine compound. The base polymer is at least one selected from polyols and urethane prepolymers, The content of the fluorine compound is 0.05 to 1.5 parts by weight relative to 100 parts by weight of the base polymer. The surface tension of a 0.1% toluene solution of the fluorine compound is 26.0 mN / m to 27.0 mN / m. The surface free energy of the adhesive layer surface with respect to diiodomethane is 6 mJ / m 2 ~30mJ / m 2 .
2. The surface protection film according to claim 1, wherein The content of the ionic compound is 0.2 parts by weight or more based on 100 parts by weight of the base polymer.
3. The surface protection film according to claim 1 or 2, wherein The adhesive layer contained in the surface protection film is bonded to a glass plate and left at 23° C. for 30 minutes. Then, the surface protection film is peeled off from the glass plate at 23° C. at a peeling angle of 180 degrees and a peeling speed of 300 mm / min. The peeling force is 0.005 N / 25 mm to 0.1 N / 25 mm. 4 . An optical member having the surface protection film according to claim 1 bonded thereto. 5 . An electronic component having the surface protection film according to claim 1 bonded thereto.
Citation Information
Patent Citations
Paint composition
JP1992275379A
Coating resin composition
JP1996012921A
Method for treating surface of outdoor article
JP1996012922A
Composition for fluororesin coating
JP1996231919A
Antistatic treatment method
JP1997165460A